Sulfur substitution in CoCu catalysts: Synergistic modulation of electronic structure and adsorption behavior for efficient 5-hydroxymethylfurfural electrooxidation - Xifan Yuan; Xin Wang; Yehan Tao; Jian Du; Jinwen Hu; Chenglong Fu; Jie Lu; Yanna Lv; Haisong Wang (Biomass and Bioenergy, 2027)

Antifungal effects of carvacrol on Penicillium verrucosum growth in refrigerated wet noodles - Hao Li; Ying-Ying Wang; Yang-Yong Lv; Huan-Chen Zhai; Yuan-Sen Hu; Fu-Zhuan Wang; Liang Huang; Shuai-Bing Zhang (International Journal of Food Microbiology, 2026)

F-doped FeNC catalyst with axial ligand engineering: breaking the strong adsorption barrier for efficient non-radical peroxymonosulfate (PMS) activation and antibiotic removal - Yuxuan Lv; Xiaoyu Shao; Yang Tao; Liang Ouyang; Zekang Li; Qing Fu; Sanying Hou (Environmental Research, 2026)

Pyrolysis-free construction of molecular-layered FePc/NiFe-LDH interfaces for electronic-state regulation and scalable bifunctional oxygen electrocatalysis - Shijian Huang; Yi Gao; Yunming Li; Qianqian Zhou; Xiang-Feng Yang; Panpan Sun; Xiaowei Lv; Xiaohua Sun; Hui Zhou; Hua-Hua Fu (Chemical Engineering Journal, 2026)

Heat-tolerant flexible pressure sensor with ultra-broad linear range for high-temperature object recognition - Yugang Chen; Shasha Wang; Shuting Xie; Haopeng Wang; Qifei Lv; Xun Fu; Huan Gao; Jiangtian Tan; Yuyu Liu; Linghai Xie (Chemical Engineering Journal, 2026)

Laminarin sulfate from Lessonia flavicans as a potential non-animal anticoagulant with minimal hemorrhagic risk: Structural characterization by NMR spectroscopy and activity analysis - Minghao Shi; Jiewen Fu; Xiang Shi; Xusheng Lv; Yonghong Liu; Qingxia Yuan; Longyan Zhao (Carbohydrate Polymers, 2026)

Toward a sustainable biorefinery of intestinal mucosa: Green extraction of heparin and valorization of co-products rich in glycosaminoglycans and bioactive peptides - Zetao Wang; Hong Lv; Zhongquan Zhao; Yongju Zhao; Yu Fu; Wei Wu (Trends in Food Science & Technology, 2026)

Development of a frequency-domain wave load mapping methodology and its initial application to a 15 MW semi-submersible floating wind turbine - Shuijin Li; Rutian Wan; Yichao Lv; Ling Wan; Jie Fu; Ben He; Yulong Li; Torgeir Moan (Ocean Engineering, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Regeneration of deep eutectic solvents: Technologies, mechanisms, applications, and challenges - Yiming Tang; Zhaonan Sun; Anping Li; Chunru Lv; Zhongxue Fu; Zhongtian Fu (Journal of Environmental Chemical Engineering, 2026)

Multiscale protection of anthocyanin via zein/cinnamaldehyde/sodium alginate core-shell nanoparticles enable UV-stabilized colorimetric label for monitoring shrimp and fish freshness - Zhihang Xu; Hong He; Jian Du; Peng Shan; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Yanna Lv; Haisong Wang (Food Chemistry, 2026)

Synergistic vacuum steam pulse blanching and gliding arc cold plasma pretreatment enhances drying efficiency and folate retention in Yardlong bean pods - Samuel Ariyo Okaiyeto; Fan Yang; Dan Liu; Lei Fu; Shi-Han Yu; Xiao-Xiao Niu; Feng-Lun Zhang; Cheng Zhang; Feng-Kui Xiong; Mohsen Mokhtarian; Weiqiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Development of ammonia-sensitive carboxymethyl cellulose/pectin colorimetric films with sodium lignosulfonate-regulated ZIF-67 for pork freshness monitoring - Zhihang Xu; Jian Du; Peng Shan; Yali Zhao; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Yanna Lv; Haisong Wang (Food Bioscience, 2026)

Cell-free Lacticaseibacillus rhamnosus-fermented cereal fraction attenuates 5-fluorouracil-induced intestinal mucositis in mice: Associations with redox homeostasis and epithelial structural preservation - Wenhui Fu; Xuemeng Ji; Dongze Qin; Lingda Zhao; Huan Lv; Yaozhong Hu; Ruican Wang; Wentao Gu; Dongfei Tan; Shuo Wang (Food Bioscience, 2026)

Enhanced microwave absorption in hierarchical magnetic carbon hollow microtubes enabled by morphological and polarization engineering - Sihai Lv; Hui Luo; Yongzhi Cheng; Fu Chen; Xiangcheng Li (Chemical Engineering Journal, 2026)

Two-pronged strategy of pore size sieving and recognition sites tailoring for perfluoropropylene-perfluoropropane separation - Zongzhen Han; Meiting Wang; Meng Gao; Kunhua Wang; Hao Yu; Zhiguo Bian; Ruitao Lv; Wei Chen; Liangmin Ning; Min Fu (Chemical Engineering Journal, 2026)

Internal plasticization and in-situ siloxane crosslinking synergistic strategy for enhancing wet-state strength and flexibility of regenerated cellulose films - Han Gao; Ao Zhai; Ajoy Kanti Mondal; Jinwen Hu; Yehan Tao; Yanna Lv; Jian Du; Chenglong Fu; Haisong Wang (Carbohydrate Polymers, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Retrieval-assisted feature fusion of SAR image and bounce-coded RCS for aircraft classification - Shangchen Feng; Xikai Fu; Yanlin Feng; Xiaolei Lv (International Journal of Remote Sensing, 2026)

Wetting-induced collapse of loess: Multistage microstructural evolution of particles and pores - Longlong Lv; Yaoxing You; Yukuai Wan; Yingpeng Fu (Transportation Geotechnics, 2026)

Digital infrastructure construction and urban green transition: A quasi-natural experiment based on the broadband China policy using double machine learning - Tiangui Lv; Xianzhe Huang; Menghan Yuan; Gui Jin; Qiao Zhao; Shufei Fu (Sustainable Cities and Society, 2026)

Nanoconfined iron-based catalysts activate peroxymonosulfate via electron transfer and radical pathways for efficient bisphenol A removal - Mingyu Sun; Qingqing Hao; Jingxingyu Wu; Chenye Fu; Long Lin; Guochun Lv; Shihuai Deng; Xiaohui Lu; Jiali Peng (Journal of Hazardous Materials, 2026)

The content, bio-accessibility and in vitro bioavailability of lead species in various seafood samples collected from Fujian, China - Siyi liu; Ying Peng; Yuting Yang; Wenchao Lv; Jingguang Li; FengFu Fu; Yue Lin (Journal of Hazardous Materials, 2026)

Ion-shielded emulsions enabling salt stability and synergistic pH-responsive release for high-salinity food preservation - Peng Shan; Jian Du; Zhihang Xu; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Jijuan Cao; Dong Lv; Haisong Wang (Food Packaging and Shelf Life, 2026)

Seismic response and critical acceleration analysis of anti-dip stratified rock slopes: Insights from shaking table tests and numerical simulations - Yang Wang; Qing Lv; Wenxi Fu; Leilei Jin; Fei Ye; Shuai Zhang (Engineering Geology, 2026)

Atrazine induces Alzheimer's disease-like neurotoxicity by targeting SDHB and disrupting synaptic function: An integrated bioinformatic and in vivo study - Yanming Lv; Yuxuan Jia; Bing Xu; Chunlong Zhao; Wenhao Fu; Yinan Zhang; Baixiang Li; Xueting Li (Chemico-Biological Interactions, 2026)

Constraint or promotion? Revealing linkages between environmental regulation and green technology diffusion in the Yangtze River Delta Urban Agglomeration - Tiangui Lv; Qiao Zhao; Gui Jin; Shufei Fu; Anying Chen (Environment, Development and Sustainability, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

First insights into PM2.5-bound photoinitiators in the Yangtze River Delta, China - Wei Zhang; Zechen Yu; Qin Lv; Xi Wang; Wenyu Xu; Shunyao Wang; Chenqi Guo; Xuezhi Yang; Jianjie Fu; Haiyan Zhang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Machine-learning-assisted process interpretation of composting time across composting systems involving multiple organic wastes: Key explanatory contributions of temperature evolution during the cooling–maturation phase - Xia Yao; Weilin Fu; Chun Song; Xueyan Zhang; Shiyu Lv; Yongzhen Ding; Feng Wang (Journal of Environmental Management, 2026)

Decrypting spatiotemporal evolution and influencing factors of cultivated land use carbon compensation in the middle reaches of Yangtze River: An interpretable machine learning approach - Tiangui Lv; Menghan Yuan; Qiao Zhao; Xianzhe Huang; Shufei Fu; Wang Li (Journal for Nature Conservation, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Self-crosslinking emulsion gels stabilized by thiolated pectin for high-efficiency curcumin encapsulation: A crosslinker-free strategy - Lv Ya-Nan; Wang Ping-Ping; Fu Xiong; Chen Chun (Food Chemistry, 2026)

Enzyme-specific release dynamics of umami and bitter peptides from shrimp processing by-products: a machine learning-aided study - Jiasi Li; Jiayuan Chen; Hong Lv; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Food Chemistry, 2026)

A flexible piezoresistive pressure sensor with an interlocking microstructure based on modulated corona electric field - Chenghang Yu; Jian Xu; Fu Lv; Bing Liu; Juan Li; Xin Li; Zijian Hong; Yongjun Wu; Yuhui Huang (Chemical Engineering Journal, 2026)

Enhancing 5-hydroxymethylfurfural electrooxidation by NiFe LDH/G-C3N4 heterojunction with π-electron mediated enhanced electron transfer - Xifan Yuan; Yehan Tao; Jialu Song; Jian Du; Jinwen Hu; Chenglong Fu; Jie Lu; Yanna Lv; Haisong Wang (Biomass and Bioenergy, 2026)

Extreme rainstorm on 15 July in Nanyang: Causes and comparison with regional typical events - Danhong Fu; Hongchao Liu; Fengxian Lu; Junjie Ma; Liyao Wu; Kaibo Wei; Chunjin Lv; Wenhu Chen; Qingbin Fan (Theoretical and Applied Climatology, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Experimental study on the configuration inversion method for flexible pipes - Wen-hua Wang; Chuang Liu; Lei Wang; Xin Lv; Yi-ming Zhang; Zhi-fu wang Yang; Hao Yang; Lei-lei Dong; Gang Liu; Ying-ying Wang; Hai-bo Sun (Ocean Engineering, 2026)

Cannabidiol alleviates D-galactose-induced muscle tissue aging in mice by modulating oxidative stress and is associated with alterations in gut microbiota - RuiXue Lv; Song Liu; Lili Liu; Li Yang; Meng Zhang; Shuai Li; Tianfei Yu; Ming Zhao; Xuepeng Fu; WeiWei Zhang (Food Bioscience, 2026)

The synergistic effects of Algal and Bryophyte colonization on soil formation and microbial community assembly in acidic mine tailings - Xinyue Wang; Ang Lv; Yaojia Fu; Zhengyan Wang; Xiangjun Zhou; Lanzhou Chen (Environmental Research, 2026)

Hydrogen peroxide modified Mg-MOF derived defective oxide: Efficient catalytic oxidation of ATP for phosphorus recovery while sterilizing and removing algae using natural light - Tian Yuan; Pu Yang; Shiyu Lv; Kerong Fu; Qiuxian Zhang; Xia Yao; Yanli Luo; Feng Wang (Chemical Engineering Journal, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Transparent cellulose films: Preparation, functionalization, and applications in food packaging - Han Gao; Ao Zhai; Linmin Xia; Jinwen Hu; Yehan Tao; Yanna Lv; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Carbohydrate Polymers, 2026)

Two-Stage Automatic-Transfer Geological Mapping Method Based on Multisource Data Fusion - Yadong Xu; Congyong Tao; Yushuai Yu; Xiaoning Guo; Mengzhi Lv; Shihui Zhang; Wenqian Fang; Wenxiao Zhou; Yunhai Zhu; Lihua Fu (Mathematical Geosciences, 2026)

Detection, isolation and molecular characterization of Senecavirus A in porcine semen: Implications for control programs - Xiaozhan Zhang; Xiuqing Li; Yiwen Liu; Nannan Lv; Beibei Yang; Shihao Fu; Zenghai Jiang; Pandeng Zhao; Yunze Guo; Jinxing Song; Chuanzhou Bian; Decheng Yang; et al. (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The EAR-motif-containing adaptor protein ECAP enhances the assembly of PYR1–ABI1 complex to promote ABA signaling in Arabidopsis - Xing Li; Changjiang Li; Gaofeng Lv; Lei Shi; Shulong Tan; Xi Li; Kaixi Liu; Anxing Li; Lei Zhu; Guanghui Yang; Jigang Li; Ying Fu (Molecular Plant, 2026)

Novel FeWO4@In2O3 Z-scheme heterojunction for enhanced photo-Fenton degradation of water pollutants - Xiaoxiao Li; Ke Song; Weiguang Lv; Han Li; Shengyu Jing; Huagen Liang; Fu Chen; Panagiotis Tsiakaras (Journal of Water Process Engineering, 2026)

When inequality suppresses aspiration: Income gaps and developmental consumption in rural China - Guoxiong Zhao; Yiyi Fu; Yunhao Lv; Xianli Xia (Journal of Rural Studies, 2026)

Internal recirculation enhances sulfide-driven autotrophic denitrification in nitrate-rich saline wastewater under coupled salinity and sulfide stress - Jiazheng Ding; Jiahao Liang; Fu Wen; Qinghong Wang; Changgang Li; Wenyu Xie; Ziwei Lv; Dingyuan Chen; Ximin Lai; Xiaoqing Chen; Dehao Li (Journal of Environmental Chemical Engineering, 2026)

Source apportionment and health risk prioritization of groundwater contamination in a coal-mining area: An integrated SOM-PMF-Monte Carlo framework - Zheng Yin; Shiqi Zhang; Xiao Fu; Ran Sun; Ran Lv; Meng Yuan; Ziyuan Gao; Gang Wu (Journal of Environmental Management, 2026)

Generalized interpolation phase field material point method for mixed-mode rock fracture - Xiao-Ping Zhou; Chi Lv; Liang-Fu Xie (International Journal of Rock Mechanics and Mining Sciences, 2026)

Controlled synthesis of micro-flexible fluorine-neodymium nanosheets for separation membranes with enhanced properties - Shurui Han; Hui Ye; Jing Lv; Xiaojian Fu; Hong Li; Yuzhong Zhang (Chemical Engineering Journal, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Nanostructured interfaces in thermoplastic/thermosetting polymer blends for enhanced high-temperature capacitive energy storage - Chengjun Fu; Jingyuan Yang; Hao Chen; Ding Ai; Ziyu Lv; Yongbiao Zhai; Shuangwu Huang; Qiyan Zhang (Chemical Engineering Journal, 2026)

Skin-inspired cellulose-based hydrogel design with hydrophobic-conductive synergy for enhanced electrochemical nanoplastic removal - Wenqin Zhong; Yehan Tao; Jialu Song; Jian Du; Jinwen Hu; Chenglong Fu; Jie Lu; Yanna Lv; Haisong Wang (Carbohydrate Polymers, 2026)

Sevoflurane activates ATF4/NSUN7/PRKCD axis to induce neurotoxicity and cognitive impairment by promoting neuron mitochondrial fission - Qiang Fu; Ling Chen; Xiong Zeng; Cuilin Lan; Guanhua Wang; Shujia Li; Tingmin Lv; Hanwen Chen (Chemico-Biological Interactions, 2026)

Study on the synergistic efficacy and mechanism of CD24 silencing combined with trastuzumab in HER2-positive breast cancer - Yi Lu; Xinglu Zhou; Yue Gao; Zi Zhu; Bao Deng; Wubin Lv; Zhenkun Fu; He Ding; Lei Zhong (Journal of Molecular Histology, 2026)

Fish community and its relationships with environmental factors in the Jiupan River, a secondary tributary of the Three Gorges Reservoir - Junquan Ren; Zhenxin Chen; Kaiyang Wu; Lilong Chen; Rongchao He; Mengqiao Long; Yankun Shen; Hanlin Wang; Mei Fu; Hongjian Lv; Weizhi Yao (Environmental Biology of Fishes, 2026)

Two-dimensional mesoporous titania at hectogram level assembled on liquid interface as efficient zinc anode protector - Tong Fu; Bingxian Chu; Wanhai Zhou; Yu Hao; Rongyao Li; Zirui Lv; Lu Liu; Yalin He; Wendi Wang; Lanhao Yang; Kun Lan (Chemical Engineering Journal, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

Quantifying soil micro-element state distribution and predicting tillage performance during sodic saline-alkali subsoiling based on mathematical model and DEM simulation approach - Min Liu; Jinchun Sun; Pinyan Lv; Dongyan Huang; Da Qiao; Yingjie Guo; Weizhi Feng; Daping Fu; Limin Jiang; Jingli Wang (Computers and Electronics in Agriculture, 2026)

Understanding roles of different radicals (·OH, SO4·- and ClO·) in the thiacloprid degradation - Guochun Lv; Yunxi Fu; Guiyin Wang; Zhang Cheng; Zhanbiao Yang; Changlian Xu; Xin Qi; Junzhuo Cai; Xiaoxun Xu (Journal of Environmental Management, 2026)

An external blank matrix-free fluorescence sensing platform based on the oxidase-like activity of CuFe2O4 magnetic particles for detecting casein phosphopeptide - Kaixin Liu; Hongxuan Zhang; Zhihong Guan; Huihui Su; Fangzhou Lv; Li Fu; Li Jia (Food Chemistry, 2026)

Structural characterization and hypoglycemic mechanisms of a Hericium coralloides heteropolysaccharide (HCP-2b) via gut microbiota modulation and PI3K/Akt signaling - Mengyu Wang; Hao Fu; Guoying Lv; Ruimeng Zhao; Weiming Cai; Xionge Pi; Zuofa Zhang (Carbohydrate Polymers, 2026)

The effect of B/N co-doping in lignin-derived carbon on CO2 sorption from flue gas - JiWen Fu; Hong Tian; ZiQi Tang; ZhangJun Huang; Lei Liu; Tan Gao; SiJin Chen; MingHao Lv (Biomass and Bioenergy, 2026)

Tubuloside B Alleviates Aβ25-35 Induced PC12 Cell Injury by Attenuating Pyroptosis, Apoptosis and Excessive Autophagy - Hao Yang; Rao Fu; Yueyang Duan; Yongjiao Hua; Tianyu Wei; Guiping Li; Xinru Gu; Ming Li; Xiao Yu; Liang Li; Liang Cao; Zhen-zhong Wang; et al. (Neurotoxicity Research, 2026)

Quercetin inhibits glycolysis and tumor progression in a cell line-dependent manner, involving PI3K/AKT signaling predominantly in HOS cells - Yang Zhou; Liquan Wang; Kang Cheng; Jingwen Chen; Jiale Lv; Chao Song; Zhijiang Fu; Zongchao Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Synergistic interactions between EM inoculants and organic fertilizers promote ecosystem recovery by restructuring fungal communities in alpine permafrost mining areas - Zongcheng Cai; Jianjun Shi; Liangyu Lv; Pei Gao; Shouquan Fu; Yu Liu; Qingqing Liu; Fayi Li; Hairong Zhang; Shancun Bao (Journal of Soils and Sediments, 2026)

The role of the nasal microbiome in linking ozone pollution to allergic rhinitis in children - Hao Tang; Shuang Du; Yongqiang Tan; Wen Su; Zhiping Niu; Jin Sun; WenPu Shao; Xinyi Fang; Zhiwei Tang; Dongjun Zhang; Zhuoru Chen; Zhenhua Zhang; et al. (Journal of Hazardous Materials, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Fracture identification in hot dry rock using TSD-Unet: From feature extraction to quantitative analysis of geometric parameters - Mangu Hu; Tianyu Fu; Xiaobin Yang; Lei Peng; Chun Wang; Xiangfeng Lv (Geothermics, 2026)

Advancements in metal-organic frameworks for alkaline oxygen evolution reaction: mechanistic insights, catalyst stability and applications - Ruo-Jin Liu; Xue-Ying Yang; Zheng-Yi Wu; Na Xu; Fu-Li Wang; Ren-Qing Lv; Guanqun Han; Bin Dong; Yong-Ming Chai (Fuel, 2026)

Hyaluronic acid–butyrate conjugates for barrier restoration in atopic dermatitis: CD44-mediated retention and inflammation-responsive release - Ting Liu; Guorong Chen; Chunxiang Zhao; Jiajia Fu; Agui Xie; Beilei Cai; Luyong Zhang; Huixia Lv (Carbohydrate Polymers, 2026)

Structure–activity relationship of a potent anti-FXase and antithrombotic chondroitin sulfate–dermatan sulfate hybrid bearing 2,3-O-sulfated motifs from Anthenoides laevigatus - Xiang Shi; Minghao Shi; Jiewen Fu; Xusheng Lv; Liang Zhang; Qingxia Yuan; Longyan Zhao; Baoshun Zhang (Carbohydrate Polymers, 2026)

Creep Behavior and Constitutive Modeling of Lacustrine Soft Soil - Guihai Fu; Ming Lv; Yangqian Ou (Geotechnical and Geological Engineering, 2026)

Driving factors and multi-scenario simulation of ecological resilience in the middle reaches of the Yangtze river metropolitan area - Shufei Fu; Yishen Liao; Tiangui Lv; Qiao Zhao; Anying Chen; Menghan Yuan; Chunguang Hu; Houbao Fan (Environment, Development and Sustainability, 2026)

Chrodrimanins U and V, meroterpenoids from an Alternaria sp. - Peinan Fu; Tingnan Zhou; Feng Guo; Jiaxin Li; Liancheng Liu; Zhiyang Lv (Natural Product Research, 2026)

Multi-media distribution, partitioning, and risks of tire additives and their transformation products in coastal waters of China - Chao Liu; Shuang Lu; Min Lv; Longwen Fu; Mingsan Man; Yize Du; Jing Ding; Wei Liu; Lingxin Chen (Marine Pollution Bulletin, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

Enhancing aerobic granulation for recalcitrant wastewater treatment in continuous-flow systems via zonal retrofit and cyclic alternating aeration-sludge recirculation - Xiaoqing Chen; Jiahao Liang; Jiazheng Ding; Qinghong Wang; Changgang Li; Wenyu Xie; Fu Wen; Ziwei Lv; Xuan Sun; Chunmao Chen; Dehao Li; Jing Liu (Journal of Water Process Engineering, 2026)

Synergistic enhancement of bisphenol A photodegradation by BiOCl via nitrite-induced charge separation and reactive oxygen species generation: A dual role for nitrite in pollutant degradation and transformation - Zengkai Fu; Zili Lin; Junle Jian; Siling Zhang; Fengyuan Zhang; Yanfang Wang; Yunshuang He; Linsheng Liu; Yishun Wang; Hongda Zhan; Zheng Hu; Ping Chen; et al. (Journal of Environmental Chemical Engineering, 2026)

Self-assembly of bayberry-like porous BiVO4 nanospheres for self-powered marine underwater optical communication - Ping Wang; Shuai Ren; Kun Fu; Yizhou Lv; Yayue Wang; Ping Rong; Weipeng Chen; Jianhua Zhang; Xifei Li; Qi Yu (Chemical Engineering Journal, 2026)

Water vapor-mediated cellulose skeleton enhances liquid-free ion-conductive elastomers for flexible electronics - Zongming Lv; Hongping Li; Meilin Zhang; Yuanyuan Lao; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Chemical Engineering Journal, 2026)

Integrated self-powered wearable system for respiratory biomarker detection based on 2D layered conductive composites - Cheng Chen; Zhaorun Tang; Caihong Lv; Donglei Fu; Xianwen Ke; Yuanquan Liu; Liangzhe Chen; Xinghai Liu (Chemical Engineering Journal, 2026)

Preparation of porous SPES/PES cation exchange membrane with interconnected spongy morphology for membrane capacitive deionization - Xiaojian Fu; Shurui Han; Jing Lv; Hui Ye; Jinli Zhao; Yuzhong Zhang (Chemical Engineering Journal, 2026)

Insight into electrocatalytic activity of lattice-confined phosphorus in activated carbon fiber for recalcitrant pollutant degradation - Hao Zhang; Hua Zheng; Shaoyan Lv; Jun Lu; Minghao Fu; Li Cai; Quanyuan Chen (Journal of Environmental Management, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Monomeric thiomolybdate ions decorated-MOFs for enhanced Hg(II) removal from water: Performance and mechanism - Chunyu Lv; Kaixing Fu; Xia Liu; Yijing Xia; Zhuoya Fang; Junfeng Zhang; Jinming Luo (Chemical Engineering Journal, 2026)

Atomically dispersed Pd on WO3/WS2 nanoflowers for fast hydrogen detection - Jingyun Li; Fanfang Meng; Mei Zhu; Hao Lv; Yanlong Gong; Xiaohong Yang; Jiangcheng Li; Shixian Xiong; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Development of an environmentally sustainable composite incorporating phosphogypsum aggregate: a perspective for enhancing interfacial stability - Shiyuan Fu; Chiqiu Wu; Wei Lv; Yuan Feng; Xue Liu; Yuxin Zhou; Kangning Liu; Rui Yu (Innovative Infrastructure Solutions, 2026)

Spatial and temporal evolution of wetland ecological quality in the Yellow River Delta: a comprehensive analysis based on multi-temporal remote sensing and improved ecological indices - Ruifeng Liu; Lansong Lv; Yurong Cui; Wenxin Pan; Xiulong Zhang; Juan Fu (Advances in Space Research, 2026)

Using UAV multispectral image data to monitor the nitrogen status of head cabbage shoots in the Liupan Mountain area of China - Shuai Wang; Long-Guo Wu; Hua Ma; Kelsang Choron; Fu-Shun Zheng; Zhong-Ting Song; Cui Yin; Hong-Yan Zhu; Peng-Yuan Lv; Yun-e Cao (International Journal of Remote Sensing, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Rapid iron redox cycling for nanoplastic and antibiotic electro-Fenton remediation by FeCo alloy on cellulose-derived carbon - Jialu Song; Yehan Tao; Zhicheng Wang; Ajoy Kanti Mondal; Jian Du; Jinwen Hu; Chenglong Fu; Jie Lu; Yanna Lv; Haisong Wang (Journal of Environmental Management, 2025)

Neurophysiological and multimodal sensory evaluation of baijiu and food pairing liking - Yu Fu; Cheng Wang; Guoliang He; Shaohui Fan; Deliang Wang; Gaochong Lv; Lucas P.J.J. Noldus; Ting Jiang; Jie Huangfu (Food Research International, 2025)

On-demand cinnamaldehyde releasing from gelatin-based active hydrogel activated by lactic acid for pork meat preservation: A novel “one-step-ahead” strategy - Peng Shan; Jiaming Wu; Jian Du; Chenglong Fu; Jinwen Hu; Yehan Tao; Jie Lu; Yanna Lv; Xiaodong Xia; Jijuan Cao; Haisong Wang (Food Chemistry, 2025)

Responses of δ13C and δ15N in Carex parvula to Ecological Restoration and the Coupling Mechanism with Soil Versatility in Alpine Regions - Fayi Li; Pingna Yin; Liangyu Lv; Shancun Bao; Zongcheng Cai; Shouquan Fu; Jianjun Shi (Ecological Engineering, 2025)

Task-specific deep eutectic solvents: Intelligent molecular design for on-demand CO2 capture and release - Xuanang Fu; Huajie Qiu; Anteng Dai; Qinghai Long; Chao Liu; Zuoming Zhou; Guohua Jing; Bihong Lv (Chemical Engineering Journal, 2025)

Vapor-phase polymerization of polypyrrole in PVA hydrogels for enhanced electrical conductivity in multimodal sensing applications - Ruobing Tian; Yu Zhang; Yuanna Sun; Jiahao Liu; Xueming Tang; Jinlong Gao; Guixin Lv; Yan Jiang; Jun Fu (Chemical Engineering Journal, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Ultrasonic high efficiency preparation of arctigenin from the fruits of Arctium lappa L using Aspergillus niger with deep eutectic solvent assisted - Yubin Ren; Shuang Jin; Weili Liu; Cailiang Peng; Hongyao Cai; Huayong Zhao; Yupeng Cheng; Yujie Fu; Na Zhang; Siyuan Wang; Chen Lv (Biotechnology Letters, 2025)

Research advances of nano chitin in the food industry: Focusing on physiological mechanisms of gut modulation - Yue Tian; Zhou Chen; Jiran Lv; Yongguo Jin; Ok-Hwan Lee; Nikolai Kuhnert; Shaoqing Yang; Zhengqiang Jiang; Xing Fu (Trends in Food Science & Technology, 2025)

Insights into the multi-media spatiotemporal distribution, partitioning, and risks of pharmaceuticals and personal care products in the southern Bohai Sea - Shuang Lu; Han Chen; Min Lv; Peng Zhang; Longwen Fu; Mingsan Man; Wei Zhang; Dongliang Wang; Jing Ding; Wei Liu; Lingxin Chen (Journal of Environmental Management, 2025)

A highly efficient tungsten carbide catalyst for natural Photothermal-Driven formic acid dehydration reaction - Maoyu Xu; Cuncai Lv; Deyi Zhang; Dongyang Zhao; Yanhui Fu; Yaguang Li; Jinhua Ye (Fuel, 2025)

Chitin nanofiber-stabilized pickering emulsions loaded with citrus essential oil: Characterization and application for pork preservation - Ge Wang; Te Yu; Jiran Lv; Linhua Huang; Ok-Hwan Lee; Xing Fu (Food Research International, 2025)

Upcycling shrimp processing by-products into dual-functional peptides: Insights into bioactivity and flavor - Jiayuan Chen; Hong Lv; Jiasi Li; Qiang Zhang; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Food Chemistry, 2025)

Quantifying the contribution of different microenvironments to real-time PM2.5 exposure of rural and urban residents in southwest China - Pingshu Wang; Shaojun Lv; Nan Fu; Nan Lin; Ming Yang; Yunhang Jiang; Yuanchen Chen; Peng Zhang; Wei Du; Bo Pan (Building and Environment, 2025)

Unraveling histones: plant protectors under environmental stress unlocking the key to resilience - Jieting Wu; Jing Shang; Lei Zhao; Xiaofan Fu; Jin Lv; Sidi Lv; Chengbin Xv; Wenquan Jin; Junsheng Lv; Fang Ma; Haijuan Guo (Plant and Soil, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Investigation on the stability of loose soil slope considering the coupling effect of seepage and runoff: theoretical analysis and flume test - Yang Wang; Yufeng Wei; Fei Ye; Qianfeng Xiao; Guangcao Lv; Wenxi Fu (Bulletin of Engineering Geology and the Environment, 2025)

Experimental and Numerical Research on p-y Curve of Offshore Photovoltaic Pile Foundations on Sandy Soil Foundation - Sai Fu; Hongxin Chen; Guo-er Lv; Xianlin Jia; Xibin Li (Journal of Marine Science and Engineering, 2025)
While methods like cyclic triaxial testing and p-y model updating theory exist in geotechnical and offshore wind engineering, they have not been systematically applied to solve the specific deformation problems of offshore PV piles. This study investigates a specific offshore photovoltaic (PV) project in Qinhuangdao City, Hebei Province. Initially, field tests of horizontal static load on steel pipe pile foundations were conducted. A finite element model (FEM) of single piles was subsequently developed and validated. Further analysis examined the failure modes, initial stiffness, and ultimate resistance of offshore PV single piles in sandy soil foundations under varying pile diameters and embedment depths. The hyperbolic p-y curve model was modified by incorporating pile diameter size effects and embedment depth considerations. Key findings reveal the following: (1) The predominant failure mechanism of fixed offshore PV monopiles manifests as wedge-shaped failure in shallow soil layers. (2) Conventional API specifications and standard hyperbolic models demonstrate significant deviations in predicting p-y (horizontal soil resistance-pile displacement) curves, whereas the modified hyperbolic model shows good agreement with field measurements and numerical simulations. This research provides critical data support and methodological references for calculating the horizontal bearing capacity of offshore PV steel pipe pile foundations.

High efficiency removal of oxytetracycline hydrochloride using a novel Fe/Mn co-modified biochar activated peroxymonosulfate: Synergistic effects of Fe and Mn - Le Lv; Yafeng Li; Xiangyu Fu; Qianqian Li; Jin Tang (Process Safety and Environmental Protection, 2025)

Separation of Co and Li from spent lithium-ion battery leachate using a synergistic extraction system based on Cyanex 272 and Cyphos IL 101 - Ze-Hang Chen; Lei Xu; Chen Chen; Zong-Bin Lv; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2025)

Volatile-char interactions during biomass pyrolysis: Effect of decoupled primary and secondary interactions on product control - Anjiang Gao; Hekuan Fu; Weiwei Wu; Shihao Lv; Wenran Gao; Nanfeng Zhu; Yong Huang; Félix Mérimé Bkangmo Kontchouo; Shu Zhang (Fuel, 2025)

Characterization of phenethyl isothiocyanate nanoemulsion loaded pectin/chitosan composite film and application in beef preservation - Xiaojing Ma; Jiachen Lv; Jiale Fu; Hongshun Hao; Jingran Bi; Hongman Hou; Gongliang Zhang (Food Chemistry, 2025)

Molecular characteristics and functional differentiation of two IL-10 genes in barbel chub Squaliobarbus curriculus - Hong Yang; Beibei Qin; Jiaojiao Fu; Mengyuan Zhang; Hongquan Wang; Tiaoyi Xiao; Zhao Lv (Fish & Shellfish Immunology, 2025)

Construction of Mn-UiO-66 with enhanced charge transfer for periodate-driven degradation of sulfaisoxazole: Degradation mechanisms and pathways - Junle Jian; Jin Wu; Linsheng Liu; Fengyuan Zhang; Yanfang Wang; Yunshuang He; Siling Zhang; Zhenjun Xiao; Zengkai Fu; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

3D crosslinked semi-interpenetrating single-ion hybrid electrolytes for dendrite-free and high-voltage lithium metal batteries - Xiao Wang; Puyan Huang; Yuwei Zhong; Shicheng Zhang; Jifang Fu; Yu Ding; Liya Chen; Guorong Chen; Fei Lv; Shuai Yuan (Chemical Engineering Journal, 2025)

Synergistic catalysis of CuxFey/CeO2 bimetallic catalysts for oxidative dehydrogenation of C2H6 with CO2 - Dan Guo; Zouxuan Qi; Zelong Fu; Zhenli Lv; Li Kang; Feigang Zhao; Tongrui Wan; Shengping Wang; Xinbin Ma (Chemical Engineering Journal, 2025)

Harnessing built-in electric fields for enhanced electron transfer in biosensor for precise digital health assessment - Tian-Run Lv; Yaqiong Yang; Jia-Chen Zhang; Ling Qi; Ming-Jie Yin; Yong Li; Ken Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2025)

Energy-efficient CO₂ capture using a biphasic tertiary-amine ionic liquid with reversible phase behavior - Qinghai Long; Yutao Bai; Anteng Dai; Huajie Qiu; Xuanang Fu; Xiaoyun Chen; Chao Liu; Waseem Hayat; Bihong Lv; Guohua Jing; Zuoming Zhou (Chemical Engineering Journal, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Niobium oxide supported CoCu catalyst for electrooxidation of 5-hydroxymethylfurfural: Bimetallic synergy and interface engineering - Yuhui Huang; Yehan Tao; Xifan Yuan; Jinwen Hu; Jian Du; Chenglong Fu; Jie Lu; Yanna Lv; Haisong Wang (Chemical Engineering Journal, 2025)

Design, synthesis and antitumour activity of pyrimidine derivatives as novel selective EGFR kinase inhibitors - Cheng Zhang; Yiwen Huo; Jianfang Fu; Yue Liu; Qinjiang Zhou; Mingyue Hou; Xiaoxuan Duan; Yanna Lv; Jinxing Hu (Molecular Diversity, 2025)

Gestational Multi-metal Exposure in Relation to Anthropometric Birth Outcomes and Maternal Hormonal Profiles: A Deeper Insight Into Sex-Specific and Trimester-Specific Influences - Jinfeng Fu; Zhanlu Lv; Wenchao Zhu; Sisi Yu; Bingjun Lu; Xulong Chen; Chiqun Shan; Yuli Lin; Zhihong Huang; Yao Yao; Shaoyou Lu (Exposure and Health, 2025)

Regional variations in vegetation greening and climate change impacts on gross primary productivity and evapotranspiration in the Loess Plateau - Fen Gou; Wei Liang; Bojie Fu; Ning Chen; Weibin Zhang; Zhao Jin; Jianwu Yan; Yihe Lv; Xingguo Mo; Nan Gao (Agricultural and Forest Meteorology, 2025)

Hydroxyl Radical‐Driven Oxidation as a Key Pathway for Greenhouse Gas Production During Soil Drying–Rewetting - Xing Guo; Yongxing Lu; Jungang Yang; Fan Du; Yakov Kuzyakov; Yuanhe Yang; Shen Yu; Shuping Qin; Qinglong Fu; Xiaoying Rong; Benfeng Yin; Kai Shi; et al. (Global Change Biology, 2025)
The drying‐rewetting of soil can increase the release of greenhouse gases over a short time period and is one of the key pathways for greenhouse gas emissions in many terrestrial ecosystems, particularly in drylands. The mechanisms underlying this pulse of greenhouse gas emissions remain nearly unknown. Here, we conducted simulated soil rewetting experiments using typical cover of dryland soils (bareland, cyanobacteria/lichen‐covered soil, and moss‐covered soil). The 13 C, 15 N, and 18 O labeling techniques allowed to explore the intrinsic mechanisms of rapid carbon (C) and nitrogen (N) release from the soils following rewetting. We found that the hydroxyl radical (˙OH) was produced after soil rewetting via the rapid activation of microorganisms. The carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) production strongly decreased after ˙OH removal, whereas the methane (CH 4 ) production was not affected. The synergistic action between ˙OH oxidation and microbial enzymatic reactions increased CO 2 production. The ˙OH also stimulated the oxidation of NH 4 + to NO 3 − and dominated the N 2 O production. Our results confirm the role of ˙OH in the production of greenhouse gases and indicate that microbially mediated ˙OH oxidation mechanisms are an overlooked key pathway for the emission of greenhouse gases during the soil rewetting. In the context of climate change, the extreme weather‐induced drying‐rewetting cycles in soils are becoming more frequent, making greenhouse gas emissions via the ˙OH oxidation pathway increasingly important.

Environmental behaviors, biotransformation, and toxicological risks of PFPiAs: A comprehensive review of an emerging PFAS - Xihua Wang; Qinya lv; Y. Jun Xu; Rongbing Fu; Yueqing Xie; Chaomeng Dai; Nianqing Zhou; Yaqiang Wei; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu (Science of The Total Environment, 2025)

Soy isoflavones attenuate atrazine-induced neuroinflammation and dopaminergic neurotoxicity in the substantia nigra: Insights from the gut microbiota-LPS-TLR4/MyD88/NF-κB axis - Yinan Zhang; Yanming Lv; Yini Wang; Wenhao Fu; Xin-yu Shi; Jiaqi Liu; Jie Wen; Xueting Li; Baixiang Li (Food Bioscience, 2025)

Multi-mechanism cross-linking driven chain spacing shortening to construct polysaccharide-based active packaging films with high water resistance and intelligent controlled release - Zhihang Xu; Jian Du; Peng Shan; Yilin Wang; Leping Li; Yehan Tao; Jinwen Hu; Chenglong Fu; Yanna Lv; Zhenglei Jia; Xunyu Song; Haisong Wang (Chemical Engineering Journal, 2025)

Simultaneously tuning the pore size and structural softness on flexible metal-organic frameworks for enhanced CO2/C2H2 separation - Junjie Peng; Zewei Liu; Jian Yan; Jiqin Zhong; Chengmin Fu; Yu Yang; Chongxiong Duan; Xin Chen; Daofei Lv; Xun Wang; Feng Xu; Jing Xiao (Chemical Engineering Journal, 2025)

An ionic liquid phase change absorbent capable of low-temperature regeneration: Investigation of phase change and regeneration mechanism - Huajie Qiu; Qinghai Long; Yutao Bai; Xuanang Fu; Chao Liu; Guohua Jing; Zuoming Zhou; Bihong Lv (Chemical Engineering Journal, 2025)

Robust smartphone-assisted cellulosic smart label for real-time monitoring shrimp freshness under low temperature and high humidity conditions - Yilin Wang; Jiaming Wu; Dong Lv; Yehan Tao; Jinwen Hu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang; Jian Du (Chemical Engineering Journal, 2025)

Natural cellulose-based multifunctional architecture for electrochemical removal and detection of nanoplastic - Qingqing Wang; Wenqin Zhong; Jian Du; Jinwen Hu; Chenglong Fu; Jie Lu; Yanna Lv; Haisong Wang; Yehan Tao (Journal of Water Process Engineering, 2025)

Assessing the environmental and economic performances of 3D printing processes for manufacturing printed circuit boards - Yingying Ke; Fu Gu; Jingxiang Lv; Jianfeng Guo (Environmental Impact Assessment Review, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Discerning changes in carbon emission intensity of cultivated land utilization since agricultural green transformation: Based on the motivation-opportunity-ability (MOA) framework - Shufei Fu; Tiangui Lv; Guangdong Wu; Hongyi Li; Limeng Zhu; Xinmin Zhang (Environmental Impact Assessment Review, 2025)

Highly stretchable, self-adhesive, conductive, and tough hydrogel reinforced with cellulose nanofibers for wearable biosensor and ultrasonic nanogenerator - Yijun Fu; Junyi Zou; Yijie Wang; Zhengyu Yao; Pengfei Lv; Dingsheng Wu; Qufu Wei; Wei Zhang; Yu Jiang; Dawei Li (Chemical Engineering Journal, 2025)

Bioinspired hydrogel tactile sensor via pressure-intensified ion signals with self-healing and anti-frozen capability - Yi-Han Xue; Tian-Run Lv; Huiting Zhang; Ya-Qiong Yang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2025)

Removal of fluoroquinolone antibiotic from wastewater based on immobilized metal affinity mechanism - L Zhao; B. Jia; M. He; H. Hu; Y. Guo; G. Fu; C. Hou; S. Gao; R. Li; X. Lv (International Journal of Environmental Science and Technology, 2025)

The association between per-fluoroalkyl and poly-fluoroalkyl substances exposure and thyroid cancer: a meta-analysis - Ruyu Wang; Mengze Lv; Siqi Chen; Yueran Zheng; Zeyuan Fu; Xupu Yang; Jingjing Wang; Qianyu Liu; Yi Liu; Xiaolin Zhang; Huicai Guo; Xuehui Liu (Journal of Environmental Health Science and Engineering, 2025)

Exploring the impact of the digital economy on carbon emission intensity: A case study of the urban agglomeration in the middle reaches of the Yangtze River - Tiangui Lv; Can Geng; Shufei Fu; Qiao Zhao; Han Hu; Xinmin Zhang (Environment, Development and Sustainability, 2025)

Coordinated development of land use change and habitat quality in the border mountainous area of China: A multi-scenario perspective - Wenqiang Wan; Xinmin Zhang; Xiao Zhou; Tiangui Lv; Guoliang Xu; Shuai Fu (Environment, Development and Sustainability, 2025)

Nickel recovery as nickel foil from electroplating sludge using a combination of bipolar membrane electrodialysis and electrodeposition - Xiaoyun Wu; Jianguo Ding; Yuying Fu; Mingzhi Lv; Yaoxing Liu (Journal of Environmental Chemical Engineering, 2025)

Biodegradable and antibacterial edible films based on egg yolk granules/gelatin/CMC with e-poly-l-lysine: Application in fresh chicken meat preservation - Muhammad Moeid Khan; Shuguo Sun; Ran Shi; Lv Aichun; Ok-Hwan Lee; Xing Fu (Food Chemistry, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

BDD electrode pulsed alternating electrochemical oxidation of sulfamethazine in antibiotic wastewater: Process optimization and degradation mechanism - Simeng Hu; Yongshang Lv; Xifei Hou; Jiahao Li; Yaxuan Hou; Xiaohua Fu; Tao Xu (Environmental Research, 2025)

Cobalt phthalocyanine modified holey Graphene/Cobalt phosphide for supercapacitor electrodes - Wei Chen; Min Fu; Siyuan Yang; Liangmin Ning; Hao Yu; Meng Gao; Kunhua Wang; Meili Guan; Ruitao Lv; Nan Li; Jianming Pan (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Nutrient additions have minor impact on microbial carbon use efficiency - Qunou Jiang; Lingyuan Yan; Huimin Wang; Xiaoqin Dai; Shengwang Meng; Xiaoli Fu; Fengting Yang; Zeqing Ma; Wenjiao Shi; Wenjun Lv; Yuxin Wang; Decai Gao (Agriculture, Ecosystems & Environment, 2025)

Noise suppression in elastic reverse time migration based on optimized pseudo-stress decoupling algorithm - Wenhao Lv; Qizhen Du; Fuyuan Zhang; Xiaoyu Zhang; Zhen Zou; Li-Yun Fu (Acta Geophysica, 2025)

Multi-modal image fusion of visible and infrared for precise positioning of UAVs in agricultural fields - Xiaodong Liu; Meibo Lv; Chenyuhao Ma; Zhe Fu; Lei Zhang (Computers and Electronics in Agriculture, 2025)

Lattice-matched MnxCd1-xS@MnS heterojunction photocatalysts: High-intensity built-in electric field boosts photocatalytic U(VI) reduction - Xueting Lv; Xin Huang; Xiang Li; Xiaoying Duan; Jiajing Wu; Wenhui Shi; Chuantao Wang; Yanzhong Zhen; Feng Fu (Journal of Water Process Engineering, 2025)

Manganese vacancy and shell protection as two-pronged strategies for boosting capacitive deionization of manganese-based prussian blue analog electrodes - Guoxiang Liu; Wei Chen; Liangmin Ning; Hao Yu; Meng Gao; Linzheng Ma; Ruitao Lv; Jianming Pan; Min Fu (Desalination, 2025)

Three-step crosslinking dependent self-bending transformation of a nano-spherical mineralized collagen laden 4D printed sodium alginate scaffold for bone regeneration - Song Lv; Xiaojie Lian; Haonan Feng; Bo Yang; Zehua Liu; Tong Fu; Liqin Zhao; Di Huang (Carbohydrate Polymers, 2025)

Selective recovery of lithium from spent LiFePO4 batteries based on PMS advanced oxidation process - Zong-Bin Lv; Lei Xu; Chen Chen; Ze-Hang Chen; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2025)

Sustainable ammonia leaching for efficient nickel and cobalt recovery from mixed hydroxide precipitate - Yu Wang; Yanjuan Zhang; Caixia Lv; Guangye Wei; Long Meng; Jiajie Fu; Zhihui Yu; Jingkui Qu (Journal of Environmental Chemical Engineering, 2025)

Crystal facet regulation of Ru/CeO2 catalysts towards boosted low-temperature CO2 methanation - Guanying Liu; Jiabao Lv; Jinlong Zou; Feng Li; Hui Fu; Youhe Wang; Hongman Sun; Zifeng Yan (Journal of Environmental Chemical Engineering, 2025)

Insights into potential flavor-active peptides and taste-related compounds in Longjing teas: A comparative study of ‘Longjing 43’ and ‘Qunti’ cultivars - Kangni Yan; Jiatong Wang; Mengxue Zhou; Qunhua Peng; Abdelkader Bassiony Mahmoud; Xue Bai; Susanne Baldermann; Xinbing Jiang; Shan Feng; Yan Wu; Jianyu Fu; Zhi Lin; et al. (Food Chemistry, 2025)

Chitin nanofiber-stabilized pickering emulsion interacting with egg white protein: Structural features, interfacial properties, and stability - Zhouyi Xiong; Te Yu; Jiran Lv; Jihui Wang; Xing Fu (Food Hydrocolloids, 2025)

Ultrasound-enhanced piezoelectric activation of Fe (Ⅵ) by ZnSnO3: A novel and efficient strategy for degrading sulfonamides antibiotics in unbuffered solutions - Linsheng Liu; Siling Zhang; Junle Jian; Ping Chen; Yishun Wang; Hongda Zhan; Zengkai Fu; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Lactobacillus paracasei GF027 promotes growth and cognitive development in juvenile rats via regulating intestinal microecology and nourishing the brain - Hang Yang; Yuanyifei Wang; Haiwei Liu; Jin Wang; Dancai Fan; Yi Sun; Huan Lv; Wenhui Fu; Shuo Wang (Food Bioscience, 2025)

Alteration of Immune Function and Gut Microbiome Composition in Carassius auratus Challenged With Rahnella aquatilis - Jiaxin Huo; Xiaowei Li; Kaiyang Zhang; Hao Fu; Xiucai Hu; Aijun Lv (Journal of Fish Diseases, 2025)
Rahnella aquatilis as an emerging pathogen can cause bacterial enteritis in cyprinid fish such as crucian carp Carassius auratus . Currently, the characterisation of immune function and gut microbiome composition in C. auratus orally challenged by R. aquatilis were yet unknown. In this study, we therefore investigated the changes of histopathology, white blood cells (i.e., LEU, NEU and LYM), serum biochemical indicators (e.g., CRE, CK and CHO) and digestive enzyme activity (e.g., LYS, AST, ALT, GSH‐Px and AKP), as well as complements and immune‐related genes (e.g., C3 , F2 , LysC , TLR3 , MyD88 , TGF‐β , TNF‐α and IL‐15 ) that were significantly altered after the oral administration of R. aquatilis KCL‐5. Moreover, the gut microbiome composition and diversity were analysed by using 16S rRNA gene high‐throughput sequencing analysis. The correlation analysis showed that the high abundance of phylum Proteobacteria , Actinobacteria , Firmicutes and Fusobacteria was related to the pathogenesis of enteritis caused by oral infection. KEGG enrichment analysis indicated that fatty acid, carbon and pyruvate metabolism were significantly increased pathways ( p C. auratus by R. aquatilis infection, which will provide a scientific reference for the clinical diagnosis and prevention of bacterial enteritis in cyprinid fish.

Cxcl9 modulates aging associated microvascular metabolic and angiogenic dysfunctions in subcutaneous adipose tissue - Xin Fu; Yu Zhao; Xiwei Cui; Siyuan Huang; Yanze Lv; Chen Li; Fuxing Gong; Zhigang Yang; Xiaonan Yang; Ran Xiao (Angiogenesis, 2025)

Design optimization of bimetal-modified biochar for enhanced phosphate removal performance in livestock wastewater using machine learning - Weilin Fu; Xia Yao; Lisheng Zhang; Jien Zhou; Xueyan Zhang; Tian Yuan; Shiyu Lv; Pu Yang; Kerong Fu; Yingqiu Huo; Feng Wang (Bioresource Technology, 2025)

Synergistic evolution of hydrological and movement characteristics of Majiagou landslide and identification of key triggering factors through interpretable machine learning - Wenmin Yao; Xin Zhang; Changdong Li; Yiming Lv; Yu Fu; Robert E. Criss; Hongbin Zhan; Changbin Yan (Bulletin of Engineering Geology and the Environment, 2025)

Inactivated LMBV vaccine with nano‑aluminum adjuvant provided immune protection in largemouth bass (Micropterus Salmoides) - Xia Luo; Ruoxuan Wang; Baofu Ma; Ouqin Chang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Lihui Liu; Aijun Lv; Ningqiu Li (Aquaculture, 2025)

A specific GAGTT insertion/deletion variation in the IL-10 gene promoter alters the disease resistance of grass carp - Hong Yang; Jiaojiao Fu; Mengyuan Zhang; Xinyi Cao; Yu Xiao; Hongquan Wang; Tiaoyi Xiao; Zhao Lv (Aquaculture, 2025)

Large-scale ecological infrastructures enhance the productivity of agro-socio-ecological systems by reducing soil erosion in the Loess Plateau - Fen Gou; Wei Liang; Yan Liu; Bojie Fu; Zhenguo Wang; Weibin Zhang; Zhigang Chen; Jianwu Yan; Junyi Li; Yihe Lv (Journal of Environmental Management, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Visible-light excitable polymers with ultra-long phosphorescence afterglow achieved by boron-based dative bonds - Wei-Guang Chen; Yan-Fang Zhuang; Yan Wang; Zhi-Jian Chen; Yi-Fan Lv; Fu Song; Yu Chen (Chemical Engineering Journal, 2025)

Failure mechanism of toppling in anti-dip layered rock slope: a case study of the Xiangpingshan landslide in southwest China - Changkui Wang; Leilei Jin; Wenxi Fu; Fei Ye; Rui Qian; Guangchao Lv; Shuang Yao (Bulletin of Engineering Geology and the Environment, 2025)

Efficient and green preparation of baicalein from Radix scutellariae with deep eutectic solvent pretreated bioconversion of cellulose-based microreactor - Shuang Jin; Yubin Ren; Yupeng Cheng; Weili Liu; Cailiang Peng; Bingyou Yang; Haixue Kuang; Yujie Fu; Chen Lv; Hongyao Cai (Sustainable Chemistry and Pharmacy, 2024)

Increased global warming potential during freeze-thaw cycle is primarily due to the contribution of N2O rather than CO2 - Chunhong Zhao; Ziping Liu; Huimin Wang; Xiaoqin Dai; Shengwang Meng; Xiaoli Fu; Qunou Jiang; Wenjun Lv; Jiancheng Chen; Decai Gao (Science of The Total Environment, 2024)

Mapping urban construction sites in China through geospatial data fusion: Methods and applications - Chaoqun Zhang; Ziyue Chen; Lei Luo; Qiqi Zhu; Yuheng Fu; Bingbo Gao; Jianqiang Hu; Liurun Cheng; Qiancheng Lv; Jing Yang; Manchun Li; Lei Zhou; et al. (Remote Sensing of Environment, 2024)

Deciphering flows: Spatial correlation characteristics and factors influencing carbon emission intensity in the Yangtze River Delta - Tiangui Lv; Qiao Zhao; Shufei Fu; Gui Jin; Xinmin Zhang; Han Hu; Guoliang Xu (Journal of Cleaner Production, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Mn and P co-doped biochar catalyst for persulfate efficient degradation of tetracycline hydrochloride：Process and mechanism - Xiangyu Fu; Yafeng Li; Keqing Cui; Yihan Liu; Le Lv (Journal of Environmental Chemical Engineering, 2024)

Notch signaling regulates limb regeneration through Hes1 and HeyL in the Chinese mitten crab - Ju Li; Xiaoyan Lv; Xin Zhang; Xiumei Zhao; Yuxuan Meng; Sidi Liu; Simiao Fu; Jinsheng Sun (Insect Biochemistry and Molecular Biology, 2024)

Shell structure impacts Camellia oleifera fruit splitting during dehydration - Pei Yang; Hanyu Fu; Penggeng Sun; Liuyang Ren; Zhaohui Zheng; Jingshen Xu; Lanlan Lv; Qing Liang; Deyong Yang (Food and Bioproducts Processing, 2024)

Biomimetic mineralization synthesis of tricobalt tetraoxide/nitrogen doped carbon skeleton for enhanced capacitive deionization - Guoxiang Liu; Min Fu; Wenbin Wang; Siyuan Yang; Wei Chen; Ruitao Lv; Hao Yu; Dongmei Wang; Jianming Pan (Desalination, 2024)

Activating copper by creating low-coordinated copper sites for antibiotic detoxification through Electrocatalytic hydrodechlorination reaction - Xiangyi Tang; Fei Shen; Wei Fan; Jianhui Liu; Lingpiao Chen; Yinan Liu; Liang Ao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Ling Chen; Yan Jiang; et al. (Chemical Engineering Journal, 2024)

Inhibition of protein disulfide isomerase mitigates steroid-induced osteonecrosis of the femoral head by suppressing osteoclast activity through the reduction of cellular oxidative stress - Xin Zhang; Changgong Feng; Tao Yuan; Yi Wang; Haojue Wang; Qizhen Lu; YongShuang Lv; Ziqing Li; Chuanyun Fu; Shui Sun (Chemico-Biological Interactions, 2024)

Chemical composition, odor characteristics and risk value analysis of odorants in particleboards - Fang Yang; Xianwu Zou; Liming Zhu; Bin Lv; Yuejin Fu; Bo Liu; Lina Tang; Qian Chen (Atmospheric Pollution Research, 2024)

Search progress of pyruvate kinase M2 (PKM2) in organ fibrosis - Shumei Lv; Mengfei Cao; Jie Luo; Kewei Fu; Wei Yuan (Molecular Biology Reports, 2024)

Expression analysis of proteins and genes related to phagosome-lysosome and immunohistochemical features of Cynoglossus semilaevis upon Vibrio vulnificus infection - Hao Fu; Minghao Ye; Xiucai Hu; Aijun Lv (Aquaculture International, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

Efficient degradation of ciprofloxacin by innovative VUV/BN system: Kinetics, mechanism and toxicity assessment - Hongda Zhan; Zili Lin; Lingrong Chen; Zhenjun Xiao; Dezhu Liu; Yishun Wang; Zhihong Chen; Zhenchao Li; Zengkai Fu; Linsheng Liu; Zihong Xu; Shuyue Chen; et al. (Journal of Water Process Engineering, 2024)

Soil moisture retrieval over agricultural fields with machine learning: A comparison of quad-, compact-, and dual-polarimetric time-series SAR data - Changchang Lv; Qinghua Xie; Xing Peng; Qi Dou; Jinfei Wang; Juan M. Lopez-Sanchez; Jiali Shang; Lei Chen; Haiqiang Fu; Jianjun Zhu; Yang Song (Journal of Hydrology, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

Robust retrofits for rural house envelope considering construction quality and occupant behavior uncertainties: A MOO-integrated Taguchi method - Di Wu; Yike Zhang; Jiqiang Zhang; Hongyi Lv; Mengze Fu (Energy and Buildings, 2024)

Alkali lignin-Fe(III)-induced successive redox reaction triggered ultrafast gelation of high quality hydrogel for wearable flexible sensors and self-powered devices - Tingjun Song; Zhuang He; Hong He; Tingting Wang; Jian Du; Yanna lv; Yehan Tao; Jie Lu; Chenglong Fu; Jinwen Hu; Haisong Wang (Chemical Engineering Journal, 2024)

From conventional to cutting-edge: Exosomes revolutionizing nano-drug delivery systems - Huiyang Fu; Yinfeng Chen; Qingyao Fu; Qingqing Lv; Jing Zhang; Yang Yang; Peng Tan; Xiaozhe Wang; Ying Yang; Zhenlong Wu (Chemical Engineering Journal, 2024)

Cobalt single-site molecular Catalyst-mediated electrochemical Hydrodechlorination for detoxification of halogenated Antibiotics: Performance, reaction pathway and mechanism - Yinan Liu; Xiangyi Tang; Fei Shen; Jiahong Zou; Yanjun Yin; Zhaojie Jiao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Guangming Jiang; Hong Liu (Chemical Engineering Journal, 2024)

A straightforward strategy to modulate ROS generation of AIE photosensitizers for type-I PDT - Zhencheng Sun; Jiaxin Wang; Minghui Xiao; Kaiyu Wu; Cheng Wang; Hao Fu; Shuyi Lv; Linqi Shi; Chunlei Zhu (Chemical Engineering Journal, 2024)

A transformation and auxiliary extraction of Cr during electrokinetic removal of Cr-contaminated multilayer composite soil chamber - Junnian Wu; Ziwei Lv; Zongqian Zheng; Yupeng Fu; Jiang Li (Environmental Geochemistry and Health, 2024)

Interfacial chemical bonds enhanced photocatalytic performance of kaolinite/NiFe layered double oxide heterostructure for photocatalytic activated peroxymonosulfate - Cheng Li; Huihua Jing; Bing Lv; Donghang Zhou; Shuguang Fu; Xiong Tang; Zhengpei Wang; Weiguang Wu; Denghui Jiang (Applied Clay Science, 2024)

Neuromelanin-MRI identifies locus coeruleus and substantia nigra degeneration as key differentiators in isolated rapid eye movement sleep behavior disorder - Junyan Fu; Ye Tang; Lei Pan; Kun Lv; Xin Cao; Siting Xu; Daoying Geng; Huan Yu; Jun Zhang (Brain Imaging and Behavior, 2024)

Construction of Solid-Liquid Two-Phase Flow and Wear Rate Prediction Model in Multiphase Pump Based on Mixture Model-Discrete Phase Model Combination Method - Xin Guo; Guangtai Shi; Yexiang Xiao; Hongqiang Chai; Wenjuan Lv; Jie Fu (Journal of Marine Science and Engineering, 2024)
Blade wear is the critical problem in the operation of multiphase pump. This paper presents a numerical study of the multiphase flow of multiphase pump. The trajectory of particles in the pump is calculated by the discrete phase model. Then, the simulation results are compared with the model test results of the pump to verify the correctness of the simulation method. The results show that the particles in the impeller domain are mainly near the hub, and the particles in the diffuser domain form a agglomerated area in the middle of the flow channel. The average wear rate of the impeller is more affected by the particle size than that of the diffuser. The maximum wear rate of blade surface increases first and then decreases with the increase of particle size. According to the wear data under different particle sizes, the regression model between particle size and wear rate is fitted to predict the wear of mixed transport pump in actual operation. The research results have important reference value for the prediction of the wear performance of the multiphase pump.

A hydro-mechanical closed form solution for the minimum safety thickness of water‑resistant rock in a karst tunnel under drag force in the connected fracture - Rui Qian; Qianqi Zhang; Qianfeng Xiao; Wenxi Fu; Guangchao Lv; Fei Ye (Tunnelling and Underground Space Technology, 2024)

Corrigendum to “Biochar as a partner of plants and beneficial microorganisms to assist in-situ bioremediation of heavy metal contaminated soil” [Sci. Total Environ. 923 (2024) 171442] - Jieting Wu; Xiaofan Fu; Lei Zhao; Jin Lv; Sidi Lv; Jing Shang; Jiaxuan Lv; Shuxuan Du; Haijuan Guo; Fang Ma (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Pollution characteristics and quantitative source apportionment of heavy metals within a zinc smelting site by GIS-based PMF and APCS-MLR models - Huagang Lv; Zhihuang Lu; Guangxuan Fu; Sifang Lv; Jun Jiang; Yi Xie; Xinghua Luo; Jiaqing Zeng; Shengguo Xue (Journal of Environmental Sciences, 2024)

Egg white fermentation by lactic acid bacteria: Effects on gel characteristics and preliminary investigation of suitable genera - Xiaohui Lv; Haobo Jin; Xing Fu; Jiran Lv; Rong Chen; Manqi Shi; Yunzheng Lv; Yongguo Jin (Food Bioscience, 2024)

Research progress of protein fibrils: A review of formation mechanism, characterization and applications in the food field - Yixin Zhang; Xiaohui Lv; Adil M. Abker; Deog-Hwan Oh; Jihan Mohamed Kassem; Mohamed Salama; Xing Fu (Food Hydrocolloids, 2024)

Imidacloprid removal by modified graphitic biochar with Fe/Zn bimetallic oxides - Song Cui; Jialin Lv; Rupert Hough; Qiang Fu; Zulin Zhang; Xiaolong Dong; Xiaohu Fan; Yi-Fan Li (Environmental Research, 2024)

Enhancement of sludge dewaterability using combined technology of bioleaching and Fenton: Microscopic structure and hydrophilic/hydrophobic properties of sludge particles - Yunbei Li; Yiwen Chen; Chunyan Fu; Shuyue Han; Yuxin Zhang; Hailong Li; Jinghua Lv; Shipeng Wang (Journal of Environmental Management, 2024)

The co-assembly of spike silica nanoparticles with high affinity to nucleic acid for airborne virus detection - Xue Zhang; Yamin Yu; Kaixin Du; Wenwei Han; Jie Xue; Shanshan Li; Shangyou Lv; Jianye Fu; Xin Wang; Meng Qiu (Chemical Engineering Journal, 2024)

Thickness-induced gradient micro-wrinkle PDMS/MXene/rGO wearable strain sensor with high sensitivity and stretchability for human motion detection - Haoxia Guo; Zhenming Chu; Luming Fu; Yongming Lv; Xiaoman Liu; Xiaoxing Fan; Wei Zhang (Chemical Engineering Journal, 2024)

3D printed micro-structured hydrogel device with transmittance-changeable soft ‘armor’ camouflage for dual-encryption - Jia-Yue Zhang; Tian-Run Lv; Yi-Han Xue; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2024)

Efficient electrocatalytic nitrate reduction on molecular catalyst with electron-deficient single-atom Cuδ+ sites - Li Shi; Yiming Li; Shuxian He; Yinan Liu; Xiangyi Tang; Liang Ao; Xiaoshu Lv; Wenyang Fu; Guangming Jiang (Chemical Engineering Journal, 2024)

“Butterfly-effect” nano-platforms for cascade immune amplification and tumor clearance through multi-modal therapy and immune sensitization - Haoyu Chen; Xiaoying Kong; Jiahui Yan; Tianyi Wang; Yaqian Lv; Fenglang Zhang; Danping Liu; Yingshan Qu; Jun Fu; Wei Han; Jinsheng Shi (Chemical Engineering Journal, 2024)

Fate of florfenicol and linezolid resistance genes and their bacterial hosts during two waste treatment models in swine feedlots - Zheng Wang; Yulin Fu; Yong-Liang Zheng; Nansong Jiang; Haiyang Jiang; Congming Wu; Ziquan Lv; Henrike Krüger-Haker; Andrea T. Feßler; Stefan Schwarz; Yang Wang (Science of The Total Environment, 2024)

Recent advances and prospects of neonicotinoid insecticides removal from aquatic environments using biochar: Adsorption and degradation mechanisms - Song Cui; Jialin Lv; Rupert Hough; Qiang Fu; LiHui An; Zulin Zhang; Yuxin Ke; Zhikun Liu; Yi-Fan Li (Science of The Total Environment, 2024)

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

Transglutaminase cross-linking ovalbumin-flaxseed oil emulsion gels: Properties, microstructure, and performance in oxidative stability - Yue Tian; Shurui Wang; Jiran Lv; Meihu Ma; Yongguo Jin; Xing Fu (Food Chemistry, 2024)

Disorders of the small intestinal microenvironment in ovalbumin-sensitized mice and mitigation strategies of 2′-fucosyllactose and Bifidobacterium longum subsp. Infantis - Wenhui Fu; Ruixin Kou; Huan Lv; Jin Wang; Qiang Xie; Dongze Qin; Bowei Zhang; Huan Rao; Yang Tian; Shuo Wang (Food Bioscience, 2024)

N-desmethyldauricine from Menispermum dauricum DC suppresses triple-negative breast cancer growth in 2D and 3D models by downregulating the NF-κB signaling pathway - Wenting Liu; Yan Yu; Tao Hou; Hongli Wei; Fangbin Lv; Aijin Shen; Yanfang Liu; Jixia Wang; Dongmei Fu (Chemico-Biological Interactions, 2024)

m6A-Mediated Upregulation of lncRNA CHASERR Promotes the Progression of Glioma by Modulating the miR-6893-3p/TRIM14 Axis - Xingwei Wu; Minjie Fu; Chang Ge; Hanyu Zhou; Haoyu Huang; Min Zhong; Mengying Zhang; Hao Xu; Guoping Zhu; Wei Hua; Kun Lv; Hui Yang (Molecular Neurobiology, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Differential accumulation patterns of flavor compounds in Longjing 43 and Qunti fresh leaves and during processing responding to altitude changes - A. Bassiony; Qunhua Peng; Susanne Baldermann; Shan Feng; Kangni Yang; Yongcheng Zhang; Jianyu Fu; Haipeng Lv; Zhi Lin; Jiang Shi (Food Research International, 2024)

Machine learning-driven prediction of phosphorus removal performance of metal-modified biochar and optimization of preparation processes considering water quality management objectives - Weilin Fu; Menghan Feng; Changbin Guo; Jien Zhou; Xueyan Zhang; Shiyu Lv; Yingqiu Huo; Feng Wang (Bioresource Technology, 2024)

Boron-doped g-C3N4 supporting Cu nanozyme for colorimetric-fluorescent-smartphone detection of α-glucosidase - Qingjie Fu; Shuang Liang; Siqi Zhang; Chenyu Zhou; Yuntai Lv; Xingguang Su (Analytica Chimica Acta, 2024)

EMR-YOLO: A Study of Efficient Maritime Rescue Identification Algorithms - Jun Zhang; Yiming Hua; Luya Chen; Li Li; Xudong Shen; Wei Shi; Shuai Wu; Yunfan Fu; Chunfeng Lv; Jianping Zhu (Journal of Marine Science and Engineering, 2024)
Accurate target identification of UAV (Unmanned Aerial Vehicle)-captured images is a prerequisite for maritime rescue and maritime surveillance. However, UAV-captured images pose several challenges, such as complex maritime backgrounds, tiny targets, and crowded scenes. To reduce the impact of these challenges on target recognition, we propose an efficient maritime rescue network (EMR-YOLO) for recognizing images captured by UAVs. In the proposed network, the DRC2f (Dilated Reparam-based Channel-to-Pixel) module is first designed by the Dilated Reparam Block to effectively increase the receptive field, reduce the number of parameters, and improve feature extraction capability. Then, the ADOWN downsampling module is used to mitigate fine-grained information loss, thereby improving the efficiency and performance of the model. Finally, CASPPF (Coordinate Attention-based Spatial Pyramid Pooling Fast) is designed by fusing CA (Coordinate Attention) and SPPF (Spatial Pyramid Pooling Fast), which effectively enhances the feature representation and spatial information integration ability, making the model more accurate and robust when dealing with complex scenes. Experimental results on the AFO dataset show that, compared with the YOLOv8s network, the EMR-YOLO network improves the mAP (mean average precision) and mAP50 by 4.7% and 9.2%, respectively, while reducing the number of parameters and computation by 22.5% and 18.7%, respectively. Overall, the use of UAVs to capture images and deep learning for maritime target recognition for maritime rescue and surveillance improves rescue efficiency and safety.

Nutritional- and flavor-enhancing effects of biomass production by Rhodotorula spp. on cantaloupe juice - Ruitong Hou; Shuyu Liu; Na Lv; Baozhong Cui; Yongxue Wei; Feiyang Long; Hongfei Fu; Yunyang Wang (Food Bioscience, 2024)

Polydopamine-immobilized lysozyme for the fabrication of antibacterial films and its application in the preservation of fresh pork - Aichun Lv; Guangsen Fan; Zhe Yang; Xinyue Zhang; Muhammad Moeid Khan; Xing Fu (Food Packaging and Shelf Life, 2024)

E3 Ubiquitin Ligase ASB14 Inhibits Cardiomyocyte Proliferation by Regulating MAPRE2 Ubiquitination - Yanpeng Yang; Dongpu Ma; Bo Liu; Xu Sun; Wei Fu; Feifei Lv; Chunguang Qiu (Cell Biochemistry and Biophysics, 2024)

Tailored wastewater surveillance framework uncovered the epidemics of key pathogens in a Northwestern city of China - Haifeng Li; Fenglan He; Ziquan Lv; Liu Yi; Ziqiang Zhang; Hui Li; Songzhe Fu (Science of The Total Environment, 2024)

Biochar as a partner of plants and beneficial microorganisms to assist in-situ bioremediation of heavy metal contaminated soil - Jieting Wu; Xiaofan Fu; Lei Zhao; Jin Lv; Sidi Lv; Jing Shang; Jiaxuan Lv; Shuxuan Du; Haijuan Guo; Fang Ma (Science of The Total Environment, 2024)

Carbon fiber supported and N-doped carbon encapsulated nZVI for synergistically adsorbing and reducing uranium - Shuaishuai Guo; Guowen Peng; Qingming Zeng; Lulin Guo; Chao Zhang; Qingyan Zhang; Xijun Fu; Junwen Lv; Qingyi Zeng (Journal of Cleaner Production, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

A Proactive Intervention Study in Metabolic Syndrome High-Risk Populations Using Phenome-Based Actionable P4 Medicine Strategy - Qiongrong Huang; Zhiyuan Hu; Qiwen Zheng; Xuemei Mao; Wenxi Lv; Fei Wu; Dapeng Fu; Cuihong Lu; Changqing Zeng; Fei Wang; Qiang Zeng; Qiaojun Fang; et al. (Phenomics, 2024)

Spatial compounding of droughts and hot extremes across southwest and east China resulting from energy linkages - Boying Lv; Zengchao Hao; Qian Ma; Yang Chen; Xuan Zhang; Yongshuo Fu; Fanghua Hao (Journal of Hydrology, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

The impact of ultrasound treatment combined with flaxseed gum on the foaming properties of egg white - Yue Tian; Jingzi Pi; Jiran Lv; Yinxia Chen; Meihu Ma; Xing Fu (Food Hydrocolloids, 2024)

The role of microstructure of extracellular proteins in dewaterability of alkaline pretreatment sludge during bioleaching - Yunbei Li; Lijun Quan; Jingyu Li; Zhiwen Zhang; Jinghua Lv; Chunyan Fu; Zhiqiang Chen (Environmental Research, 2024)

3D microprinting of QR-code integrated hydrogel tactile sensor for real-time E-healthcare - Zi-Rong Li; Tian-Run Lv; Zhenxu Yang; Wen-Hai Zhang; Ming-Jie Yin; Ken-Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

Geochronology, petrogenesis, and geological significance of the quartz vein-type copper deposits in Longwei area, north-west Dayaoshan, Guangxi - Song Fu; Shehong Li; Changxing Lv; Longqing Shi; Xuhan Hu; Jinming Wu; Zhuolin Xie (Frontiers of Earth Science, 2024)

Gut microbiota dysbiosis and intestinal barrier impairment in diarrhea caused by cold drink and high-fat diet - Yajuan Tian; Meng Fu; Jie Su; Meiqiu Yan; Jingjing Yu; Chenxing Wang; Zhuangwei Niu; Yuzhong Du; Xueling Hu; Jiayi Zheng; Bai Tao; Zengguang Gao; et al. (Toxicology, 2024)

Dual strategy of ultrasound and doping enhance Mott Schottky heterojunction carrier exchange for efficient oxygen evolution - Yi-Wen Dong; Qian-Xi Lv; Bao-Hua Chen; Zheng-Yang Jin; Jing-Yi Xie; Fu-Li Wang; Chun-Ying Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

Manganese doped hollow cobalt oxide catalysts for highly efficient oxygen evolution in wide pH range - Jing-Yi Xie; Fu-Li Wang; Xue-Jun Zhai; Xin Li; Yu-Sheng Zhang; Ruo-Yao Fan; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Inhibiting effect of 2-amino-2-methyl-1-propanol on gelatinous product formation in non-aqueous CO2 absorbents: Experimental study and molecular understanding - Chao Liu; Guohua Jing; Zongqiang Zhu; Yinming Fan; Shengpeng Mo; Yanan Zhang; Dunqiu Wang; Bihong Lv; Mingming Fu; Xiaobin Zhou (Chemical Engineering Journal, 2024)

“Triple-Hop” nano-bomb combining CDT, PDT and immunetherapy for NIR-triggered cancer therapy - Haoyu Chen; Junyao Song; Youpei Wang; Tianyi Wang; Fenglan Zhang; Yaqian Lv; Zhexi Liu; Jun Fu; Xiaoying Kong (Chemical Engineering Journal, 2024)

Adaptation of Glucose Metabolism to Limb Autotomy and Regeneration in the Chinese Mitten Crab - Ju Li; Xiaohong Li; Simiao Fu; Yuxuan Meng; Xiaoyan Lv; Xin Zhang; Guozheng Liu; Jinsheng Sun (Marine Biotechnology, 2024)

Comprehensive analysis of pigment alterations and associated flavor development in strip and needle green teas - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Susanne Baldermann; Yin Zhu; Weidong Dai; Shan Feng; Jesus Simal-Gandara; Jianyu Fu; Haipeng Lv; Zhi Lin; Jiang Shi (Food Research International, 2024)

A novel self-assembled dual-emissive ratiometric fluorescent nanoprobe for alkaline phosphatase sensing - Zhixuan Han; Nan Wang; Yuntai Lv; Qingjie Fu; Guannan Wang; Xingguang Su (Analytica Chimica Acta, 2024)

Effect of glass transition on the formation of drying cracks in the component parts of maize kernels - Zhaohui Zheng; Liuyang Ren; Hanyu Fu; Pei Yang; Lanlan Lv; Jingshen Xu; Deyong Yang (Biosystems Engineering, 2023)

Exploring spatial-temporal driving factors for changes in multiple ecosystem services and their relationships in West Liao River Basin, China - Wei Jiang; Bojie Fu; Guangyao Gao; Yihe Lv; Cong Wang; Siqi Sun; Kai Wang; Stefan Schüler; Zhongguo Shu (Science of The Total Environment, 2023)

Upcycling spent lithium battery cathodes into efficient PMS catalysts for organic contaminants degradation - Lei Xu; Le Liang; Chen Chen; Ze-Hang Chen; Zong-Bin Lv; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2023)

Ultrasound-assisted glycation on ovalbumin fibrosis: A novel, efficient immobilization for lipase - Yixin Zhang; Jihong Liu; Jiran Lv; Qiuyu Li; Deog-Hwan Oh; Xing Fu (Food Bioscience, 2023)

Andrographolide inhibits the activation of spinal microglia and ameliorates mechanical allodynia - Dan Wang; Yongjian Zheng; Junjing Xie; Wenwen Yu; Zhongteng Lu; Wenping Zhang; Yanling Hu; Jianyuan Fu; Qing Sheng; Zhengbing Lv (Metabolic Brain Disease, 2023)

Revealing Heavy Metal-Resistant Mechanisms and Bioremediation Potential in a Novel Croceicoccus Species Using Microbial-Induced Carbonate Precipitation - Xuya Lv; Yingwen Zhong; Geyi Fu; Yuehong Wu; Xuewei Xu (Journal of Marine Science and Engineering, 2023)
Polymetallic nodules and polymetallic sulfides are currently the major mineral resources found on the seabed. The motivation behind deep-sea mining arises from the pursuit of valuable metals, driven by both economic and geopolitical considerations. However, before mining can be authorized, it is crucial to understand the microbial adaptation and biomineralization process related to heavy metals in deep-sea environments. To search for potential candidate materials for bioremediation in deep-sea environment, two strains with high resistance to manganese and the ability to form rhodochrosite precipitates were isolated from the deep-sea polymetallic nodule areas and hydrothermal polymetallic sulfide areas. Genomic analysis revealed that the strains employed various effective survival strategies, such as motility, chemotaxis, biofilm formation, metal redox, and transporters, to adapt to heavy metal environments. The bacterial strains Ery5 and Ery15 promote the formation of carbonate crystals by creating an excessively alkaline environment and releasing extracellular polymeric substances (EPSs). Furthermore, strains Ery5 and Ery15 were identified using polyphasic taxonomy methods and proposed as a new species belonging to the genus Croceicoccus. This study presents potential candidates for bioremediation in deep-sea environments.

Source control on the acid mine drainage produced by the oxidation of pyrite and sulfur-containing uranium tailings based on the microbially induced carbonate precipitation technology - Yao Zhang; Qi Fang; Junwen Lv; Yukui Fu; Jiahua Zhu; Guojian Peng; Mi Li; Xiaoyan Wu; Hongqiang Wang; Zhenyu Chen (Journal of Cleaner Production, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Selective electrooxidation of 2-hydroxybenzyl alcohol coupled with H2 production promoted by surface reconstruction of β-Ni(OH)2 nanosheets - Weiwei Yang; Mao Peng; Ye Lv; Mengya Sun; Jinli Zhang; Wei Li; Yan Fu (Chemical Engineering Journal, 2023)

Immunogenic necroptosis in liver diseases: mechanisms and therapeutic potential - Zirui Ye; Nana Zhang; Hong Lei; Huimin Yao; Jingya Fu; Nan Zhang; Lexuan Xu; Guxiang Zhou; Zhijun Liu; Yi Lv (Journal of Molecular Medicine, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Impact of the intensive use of urban construction land on carbon emission efficiency: evidence from the urban agglomeration in the middle reaches of the Yangtze River - Tiangui Lv; Can Geng; Xinmin Zhang; Zeying Li; Han Hu; Shufei Fu (Environmental Science and Pollution Research, 2023)

Enhancement of sludge dewaterability by repeated inoculation of acidified sludge: Extracellular polymeric substances molecular structure and microbial community succession - Yunbei Li; Chunyan Fu; Xinyu Cao; Xin Wang; Ninghao Wang; Mengyu Zheng; Lijun Quan; Jinghua Lv; Zhensheng Guo (Chemosphere, 2023)

M1 polarization of chicken macrophage HD11 can be activated by duck Tembusu virus via MyD88-NF-κB-mediated signaling pathway - Ningwei Geng; Ji Fu; Zehao Lv; Jing Li; Yuxin Kong; Lei Qu; Zhiyun Guo; Jun Zhao; Liya Zhu; Feng Wang; Cui Zhao; Sidang Liu; et al. (Veterinary Microbiology, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

Spatiotemporal evolution and convergence of agricultural eco-efficiency in the middle reaches of the Yangtze River - Tiangui Lv; Shufei Fu; Xinmin Zhang; Han Hu; Yanwei Zhang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Profiling of the spatiotemporal distribution, risks, and prioritization of pharmaceuticals and personal care products in coastal waters of the northern Yellow Sea, China - Xiaotong Guo; Min Lv; Lehui Song; Jing Ding; Mingsan Man; Longwen Fu; Shuang Lu; Lijun Hou; Lingxin Chen (Journal of Hazardous Materials, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

Two-point-one-line modularized strategy combined with Holliday-junction button probes for multiloci SNPs long-range distribution analysis - Wang Luo; You Wu; Xueping Chen; Li Zhang; Li Wang; Dan Bai; Qian Liu; Ting Wang; Hongyan Yu; Yaxing Xie; Yixin Fu; Zhongzhong Wang; et al. (Chemical Engineering Journal, 2023)

CuO2-assisting-Zn single atom hybrid nanozymes for biofilm-infected wound healing - Junyao Song; Haoyu Chen; Yaqian Lv; Wanqun Yang; Fenglang Zhang; Tianyi Wang; Danping Liu; Yingshan Qu; Lei Han; Jun Fu; Xiaoying Kong (Chemical Engineering Journal, 2023)

A zinc-octacarboxylate MOF with an unusual (6, 8)-connected ocu topology for high-capacity adsorptive separation of C8 alkylaromatics - Xiuping Deng; Maojun Deng; Yu-Lin Li; Zewei Liu; Tian-Fu Liu; Xin Chen; Shuhan Cai; Biying Liu; Jiesen Li; Daofei Lv; Jing Li; Wenbing Yuan (Chemical Engineering Journal, 2023)

Soil organic carbon stability and exogenous nitrogen fertilizer influence the priming effect of paddy soil under long-term exposure to elevated atmospheric CO2 - Hongyan Yu; Mixue Han; Chuang Cai; Fu Lv; Yue Teng; Luyi Zou; Guoqing Ding; Xuejia Bai; Junhou Yao; Kang Ni; Chunwu Zhu (Environmental Science and Pollution Research, 2023)

Decarbonizing ceramic industry: Technological routes and cost assessment - Kai Ding; Anjie Li; Jingxiang Lv; Fu Gu (Journal of Cleaner Production, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Hedgehog signaling is essential in the regulation of limb regeneration in the Chinese mitten crab, Eriocheir sinensis - Ju Li; Jinmei Zuo; Xiaoyan Lv; Jiahe Ma; Xiaohong Li; Simiao Fu; Jinsheng Sun (Fish & Shellfish Immunology, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Comparative transcriptome analysis of grafting to improve chilling tolerance of cucumber - Xin Fu; Chun-Yu Lv; Yan-Yan Zhang; Xi-Zhen Ai; Huan-Gai Bi (Protoplasma, 2023)

Microbial remediation of oil-contaminated shorelines: a review - Xiaoli Dai; Jing Lv; Pengcheng Fu; Shaohui Guo (Environmental Science and Pollution Research, 2023)

An ultra-light sustainable sponge for elimination of microplastics and nanoplastics - Jianxin Fu; Nuan Liu; Yunxi Peng; Guoqing Wang; Xiaokun Wang; Qiaoning Wang; Min Lv; Lingxin Chen (Journal of Hazardous Materials, 2023)

Preparation and performance of porous ceramsite for Ag+ removal in sewage treatment with total phosphorus tailings - Nanyan Hu; Yafei Lv; Binyu Luo; Yicheng Ye; Fanghui Fu; Jinpeng Jia; Zhibing Ou; Jiangli Li (Journal of Cleaner Production, 2023)

A novel AD theranostic platform with NIR-II laser controlled drug release and real-time monitoring of therapeutic outcomes - Zhili Qiu; Guojun Cao; Shanrong Lv; Dehong Yu; Jingjing Fu; Hanrong Yan; Yuting Li; Peng Zhou; Xiunan Wu; Zhao Liu; Fenglei Gao (Chemical Engineering Journal, 2023)

Driving mechanism of the allometric relationship between economic development and carbon emissions in the Yangtze River Delta urban agglomeration, China - Tiangui Lv; Han Hu; Xinmin Zhang; Lu Sun; Zhaoling Li; Yijing Chen; Shufei Fu (Environment, Development and Sustainability, 2023)

Enhancement of the classification and recovery process of fine mineral particles via a newly developed volute feed hydrocyclone - Wenjie Lv; Qi Wei; Yujie Ji; Bing Liu; Hongpeng Ma; Yuan Huang; Haitao Huang; Hualin Wang; Pengbo Fu (Environmental Science and Pollution Research, 2023)

Characteristics and sources of PM2.5-bound elements in Shanghai during autumn and winter of 2019: Insight into the development of pollution episodes - Yanan Chen; Xingnan Ye; Yinghui Yao; Zhixiao Lv; Zhenghang Fu; Cheng Huang; Ruoyan Wang; Jianmin Chen (Science of The Total Environment, 2023)

Ti-MOF@Metal-polyphenol network derived TiN0.9@NC/magnetic MWCNTs composites for microwave absorption - Shanshan Zhang; Guizhen Liu; Sihai Lv; YingLi Zhu; Pingan Chen; Hui Luo; Xiangcheng Li; Fu Chen (Chemical Engineering Journal, 2023)

Control of seasonal variations of precipitation isotope in Rizhao, Eastern China - Lili Shao; Mengjing Fu; Yiliang Chen; Kai Li; Xiangjuan Lv; Baofu Li (Theoretical and Applied Climatology, 2023)

The effect of vacancy defective Mg (0001) surface on hydrogenation of Ni-Mg-CNTs: A mechanistic investigation - Congwen Duan; Mengmeng Wu; Xinya Wang; Dong Fu; Yuling Zhang; Wei Lv; Lianxi Hu; Ming Li; Fei Wang; Ying Wu (Fuel, 2023)

Deletion of the cheZ gene results in the loss of swimming ability and the decrease of adhesion ability to Caco-2 cells in Escherichia coli Nissle 1917 - Bingming Ou; Haihui Lv; Hua Ge; Dexiang Fu; Xin Lin; Saiqiao Huang; Xiaojie Chen; Yufu Liu; Sainan Li; Wenhua Liu; Lihua Huang; Ying Yang; et al. (Folia Microbiologica, 2023)

Modification of ovalbumin by the enzymatic method: Consequences for foaming characteristics of fibrils - Jingzi Pi; Jia Wang; Jiran Lv; Yongguo Jin; Deog-Hwan Oh; Xing Fu (Food Hydrocolloids, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Vitamin C down-regulates the H3K9me3-dependent heterochromatin in buffalo fibroblasts via PI3K/PDK1/SGK1/KDM4A signal axis - Jinling Wang; Lei Wang; Zhiqiang Wang; Meiyun Lv; Jiayuan Fu; Yunchuan Zhang; Peng Qiu; Deshun Shi; Chan Luo (Theriogenology, 2023)

Promotion and inhibition effects of wax on methane hydrate formation and dissociation in water-in-oil emulsions - Shikun Tong; Pengfei Li; Fengjun Lv; Zhiyuan Wang; Weiqi Fu; Jianbo Zhang; Litao Chen; Xuerui Wang (Fuel, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Non-target scanning of organics from cooking emissions using comprehensive two-dimensional gas chromatography-mass spectrometer (GC×GC-MS) - Kai Song; Song Guo; Yuanzheng Gong; Daqi Lv; Zichao Wan; Yuan Zhang; Zihao Fu; Kun Hu; Sihua Lu (Applied Geochemistry, 2023)

Spatiotemporal analysis and prediction of water quality in Pearl River, China, using multivariate statistical techniques and data-driven model - HaoNan Ding; Xiaojun Niu; Dongqing Zhang; Mengyu Lv; Yang Zhang; Zhang Lin; Mingli Fu (Environmental Science and Pollution Research, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Risk assessment of Artemia egg shell-Mg-P composites as a slow-release phosphorus fertilizer during its formation and application in typical heavy metals contaminated environment - Sufeng Wang; Xiaojuan Lv; Mingwei Fu; Zijing Wang; Dan Zhang; Qina Sun (Journal of Environmental Management, 2023)

Towards effective wildlife protection law for marine species in China: A stakeholders’ perspective - Kit Yue Kwan; Ruifang Chen; Chun-Chieh Wang; Shuhao Lin; Lv Wu; Xiaoyong Xie; Zhaohong Weng; Menghong Hu; Haichao Zhou; Zhou Wu; Yijian Fu; Wenquan Zhen; et al. (Frontiers in Marine Science, 2023)
Introduction As one of the megadiverse countries, the effectiveness of wildlife protection in China is of great significance to global biodiversity conservation. With continued evolution and revisions, China’s Wildlife Protection Law has listed over 140 marine species; however, it is still inclined toward terrestrial animals. Methods To narrow the gap between compliance and enforcement, we collected 1,309 effective responses from various coastal cities of China through an anonymous online questionnaire survey, to investigate their exposure, understanding and attitudes toward Wildlife Protection Law for marine species (mWPL). Results Most respondents demonstrated an overall good understanding about the context, necessity and effectiveness of mWPL. The fisher communities were found to be more aware of the dissemination and implementation of mWPL. However, they understood less of the penal system, and exhibited negative attitudes toward the necessity and punishment of the legislation, probably due to the conflicts between resource utilizations and legislative interventions. The participants also indicated that seahorses, horseshoe crabs and corals were commonly subjected to illegal exploitations. Discussion While most respondents suggested greater fines, tighter laws and better public enforcement, we advocate the exploration of bottom-up options such as community engagement and environmental education to improve compliance and implementation of mWPL for the benefit of marine wildlife conservation in China.

Spatiotemporal heterogeneity and decoupling decomposition of industrial carbon emissions in the Yangtze River Delta urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Hualin Xie; Shufei Fu; Can Geng; Zeying Li (Environmental Science and Pollution Research, 2023)

A sustainable approach for selective recovery of lithium from cathode materials of spent lithium-ion batteries by induced phase transition - Fu Rao; Zhi Sun; Weiguang Lv; Xihua Zhang; Jie Guan; Xiaohong Zheng (Waste Management, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

Spatiotemporal coupling of multidimensional urbanization and resource–environment performance in the Yangtze River Delta urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Hualin Xie; Shufei Fu; Li Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Composition and function of viruses in sauce-flavor baijiu fermentation - Hai Du; Bowen Chen; Wenbo Fu; Fan Yang; Xibin Lv; Yuwei Tan; Xiaoli Xi; Li Wang; Yan Xu (International Journal of Food Microbiology, 2023)

Development mechanism of radial chain rockbursts in a deep tunnel excavated by TBM - Lianjie Fu; Xia-Ting Feng; Zhibin Yao; Lei Hu; Yongwei Quan; Bin Lv; Wenjing Niu; Wei Zhang (Engineering Geology, 2023)

Investigation on the vertical distribution and transportation of PM2.5 in the Beijing-Tianjin-Hebei region based on stereoscopic observation network - Tingting Sun; Tianshu Zhang; Yan Xiang; Guangqiang Fan; Yibin Fu; Lihui Lv (Atmospheric Environment, 2023)

Occurrence and risk assessment of antibiotics in feces of elderly individuals in Shenzhen - Yuan Zhang; Ziquan Lv; Xiaowei Li; Kunxia Zhao; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Science and Pollution Research, 2023)

Chitin and chitin-based biomaterials: A review of advances in processing and food applications - Jiran Lv; Xiaohui Lv; Meihu Ma; Deog-Hwan Oh; Zhengqiang Jiang; Xing Fu (Carbohydrate Polymers, 2023)

Indoor volatile organic compounds in existing densely occupied education buildings of four universities: Source apportionment - Pian Wei; Nan Fu; Xinba Lv; Yabin Jia; Xu Zheng; Jun Guan (Building and Environment, 2023)

Spatial transcriptome analysis of long non-coding RNAs reveals tissue specificity and functional roles in cancer - Kang Xu; Xiyun Jin; Ya Luo; Haozhe Zou; Dezhong Lv; Liping Wang; Limei Fu; Yangyang Cai; Tingting Shao; Yongsheng Li; Juan Xu (Journal of Zhejiang University-SCIENCE B, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Advancing parameter estimation with Characteristic Finite Difference Method (CFDM) for a marine ecosystem model by assimilating satellite observations: Spatial distributions - Minjie Xu; Yongzhi Liu; Zihan Zhao; Kai Fu; Xianqing Lv (Frontiers in Marine Science, 2022)
The ecosystem parameters are critical for precisely determining the marine ecological process and improving the simulations of the marine ecological model. In this study, based on the NPZD (nutrient, phytoplankton, zooplankton and detritus) model, the surface chlorophyll-a observations obtained from Sea-viewing Wide Field-of-view Sensor (SeaWiFS) data were assimilated to estimate spatially ecosystem parameters in the Bohai, Yellow, and East China Seas using an adjoint assimilation method with characteristic finite difference scheme. The experiments of the moving Gaussian hump indicated that the characteristic finite difference method (CFDM) can get rid of the limit of stability and permit using large time steps, which reduces long computation durations and large memory requirements. The model performance was significantly improved after data assimilation with CFDM using a large time step of 6 hours. Moreover, the distributions of parameters of the NPZD model in winter in the Bohai Sea, the Yellow Sea, and the East China Sea were simulated by our method. Overall, the developed method can efficiently optimize the ecosystem parameters and the results can be beneficial for determining reasonable parameters of the marine ecological model.

Phosphorus fractionation and adsorption characteristics in drinking water reservoir inlet river sediments under human disturbance - Zihao Fu; Zijin Hong; Junling Wei; Yukai Liao; Songlin You; Yifan Wang; Jianjing Lv; Huan Feng; Marek Kolenčík; Xuexiu Chang; Yu Qian (Journal of Soils and Sediments, 2022)

Spatiotemporal dynamics and decoupling mechanism of economic growth and carbon emissions in an urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Shufei Fu; Can Geng; Zeying Li (Environmental Monitoring and Assessment, 2022)

Correction to: Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Spatiotemporal pattern of regional carbon emissions and its influencing factors in the Yangtze River Delta urban agglomeration of China - Tiangui Lv; Han Hu; Xinmin Zhang; Hualin Xie; Shufei Fu; Li Wang (Environmental Monitoring and Assessment, 2022)

Brevibacillus dissolubilis sp. nov., Isolated from Fresh Water - Wei Li; Zhao-Xuan Wang; Fu Ma; Zhi-Da Zi; Han-Yi Chen; De Zhou; Jie Lv (Current Microbiology, 2022)

Study on Iron Extraction from High Iron Bauxite Residue by Pyrite Reduction - HuiJun Fu; GuoZhi Lv; Ting-an Zhang; Xi Chao; Yang Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

Pulmonary Infection Caused by Strongyloides stercoralis - Lingqing Xu; Qianjun He; Linjuan Chen; Jiaxi Lv; Yinxian Tang; Yuzhen Li; Zhongwen Zhang; Weihong Wen; Guoquan Zhong; Hui Liu; Bishi Fu (Acta Parasitologica, 2022)

Spatial spillover effects of urbanization on carbon emissions in the Yangtze River Delta urban agglomeration, China - Tiangui Lv; Han Hu; Xinmin Zhang; Hualin Xie; Li Wang; Shufei Fu (Environmental Science and Pollution Research, 2022)

NMMHC IIA triggered lipid metabolize reprogramming resulting in vascular endothelial cellular tight junction injury - Yanni Lv; Daojun Hong; Longsheng Fu; Yisong Qian (Molecular Biology Reports, 2022)

Empty-hole effect on fracture propagation under blasting load - Yanxin Lv; Chao Yuan; Yanzhao Fu; Xiaohua Zhu; Quan Gan; Haibo Li; Qiuyu Chen (Arabian Journal of Geosciences, 2022)

Six phenanthrenes from the roots of Cymbidium faberi Rolfe. and their biological activities - Shuang-shuang Lv; Yu Fu; Jun Chen; Yuan Jiao; Sui-qing Chen (Natural Product Research, 2022)

Failure Mechanism and Control of Surrounding Rock of Mining Roadway Under Overlying Goaf - Jiyuan Yang; Junliang Dong; Kun Lv; Zhongwei Bi; Xingyu Fu; Bin Zhao (Geotechnical and Geological Engineering, 2022)

Numerical and Experimental Analysis of Transient Flow Field and Pressure Pulsations of an Axial-Flow Pump Considering the Pump–Pipeline Interaction - Fan Yang; Zhongbin Li; Jianguo Fu; Yuting Lv; Qingwei Ji; Hongfu Jian (Journal of Marine Science and Engineering, 2022)
The internal flow in a vertical axial-flow pump is a complex unsteady three-dimensional viscous flow. An unstable flow often produces complex flow phenomena such as flow separation, vortices, and secondary reflux, which reduces the operating efficiency of the pump and can endanger safety and stability. In this paper, computational fluid dynamics is used to calculate the flow characteristics in an axial-flow pump using the shear stress transport and curvature correction (SST-CC) model for turbulence modified to account for the rotational curvature. Furthermore, the dependability of the numerical results was confirmed by a test with an actual model of a pump. The transient deviation angle at the impeller inlet of the pump, the stream field attributes in various spanwise parts of the impeller and guide vane, and the velocity distributions at the impeller inlet and outlet were analyzed. The omega method was utilized to recognize the vortex structure inside the guide vane. Moreover, the development of the transient vortex structure inside the guide vane was studied. As the flow rate increased, the scale and turbulent kinetic energy of the vortex structure gradually decreased. The time-domain graph for the impeller inlet is clearly periodic, with three peaks and three troughs in an impeller rotational period. The dominant frequency in the spectrum at each monitoring point was basically the blade frequency, and the secondary dominant frequency was twice the blade frequency.

Effect of paeonol against bacterial growth, biofilm formation and dispersal of Staphylococcus aureus and Listeria monocytogenes in vitro - Qiao Zeng; Yuting Fu; Min Yang; Ting Wang; Ying Wang; Shenghua Lv; Weidong Qian (Biofouling, 2022)

Effect of gene polymorphism on bleeding complications in Chinese Han patients taking warfarin - Xiaotong Xia; Jinglan Fu; Tingting Wu; Wenjun Chen; Shaojun Jiang; Meina Lv; Jinhua Zhang (European Journal of Clinical Pharmacology, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

To establish a model for the prediction of initial standard and maintenance doses of warfarin for the Han Chinese population based on gene polymorphism: a multicenter study - Xiaotong Xia; Nianxu Huang; Boxia Li; Yan Li; Lang Zou; Dongdong Yuan; Banghua Huang; Yufei Bei; Yuxin Liu; Jinglan Fu; Tingting Wu; Wenjun Chen; et al. (European Journal of Clinical Pharmacology, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Nucleoporin 37 promotes the cell proliferation, migration, and invasion of gastric cancer through activating the PI3K/AKT/mTOR signaling pathway - Jishui Zhang; Wenhao Lv; Yagang Liu; Weihua Fu; Baosheng Chen; Qiutong Ma; Xin Gao; Xiuxia Cui (In Vitro Cellular & Developmental Biology - Animal, 2021)

Paleoenvironment controls on organic matter accumulation in transitional shales from the eastern Ordos Basin, China - Jianwei Lv; Songhang Zhang; Ning Yang; Chunbo Fu; Xinlu Yan; Yang Li (Frontiers of Earth Science, 2021)

Accelerated increase in vegetation carbon sequestration in China after 2010: A turning point resulting from climate and human interaction - Yongzhe Chen; Xiaoming Feng; Hanqin Tian; Xutong Wu; Zhen Gao; Yu Feng; Shilong Piao; Nan Lv; Naiqing Pan; Bojie Fu (Global Change Biology, 2021)
China has increased its vegetation coverage and enhanced its terrestrial carbon sink through ecological restoration since the end of the 20th century. However, the temporal variation in vegetation carbon sequestration remains unclear, and the relative effects of climate change and ecological restoration efforts are under debate. By integrating remote sensing and machine learning with a modelling approach, we explored the biological and physical pathways by which both climate change and human activities (e.g., ecological restoration, cropland expansion, and urbanization) have altered Chinese terrestrial ecosystem structures and functions, including vegetation cover, surface heat fluxes, water flux, and vegetation carbon sequestration (defined by gross and net primary production, GPP and NPP). Our study indicated that during 2001–2018, GPP in China increased significantly at a rate of 49.1–53.1 TgC/yr 2 , and the climatic and anthropogenic contributions to GPP gains were comparable (48%–56% and 44%–52%, respectively). Spatially, afforestation was the dominant mechanism behind forest cover expansions in the farming‐pastoral ecotone in northern China, on the Loess Plateau and in the southwest karst region, whereas climate change promoted vegetation cover in most parts of southeastern China. At the same time, the increasing trend in NPP (22.4–24.9 TgC/yr 2 ) during 2001–2018 was highly attributed to human activities (71%–81%), particularly in southern, eastern, and northeastern China. Both GPP and NPP showed accelerated increases after 2010 because the anthropogenic NPP gains during 2001–2010 were generally offset by the climate‐induced NPP losses in southern China. However, after 2010, the climatic influence reversed, thus highlighting the vegetation carbon sequestration that occurs with ecological restoration.

Devosia sediminis sp. nov., isolated from subterranean sediment - Fu Ma; Zhi-Da Zi; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2021)

Nano-oxides washcoat for enhanced catalytic oxidation activity toward the perovskite-based monolithic catalyst - Chunwang Lv; Hongwei Chen; Mingjiang Hu; Tianchao Ai; Haoka Fu (Environmental Science and Pollution Research, 2021)

Lignin Synthesis Related Genes with Potential Significance in the Response of Upland Cotton to Fusarium Wilt Identified by Transcriptome Profiling - Jianan Hou; Fu’an Zhao; Xiaojie Yang; Wu Li; Deyi Xie; Zhongjie Tang; Shuping Lv; Lihong Nie; Yao Sun; Mengmeng Wang; Yajing Zhu; Xiaopei Bo; et al. (Tropical Plant Biology, 2021)
Fusarium wilt, caused by the fungus Fusarium oxysporum Schlecht. f. sp. vasinfectum (Fov) is a destructive soil-borne cotton disease. To profile the genes and pathways responding to Fov infection, we compared transcriptomic responses before and after F. oxysporum inoculation in a highly resistant cotton cultivar, Yumian21, and a highly susceptible cultivar, Jimian11. Although the overall gene expression pattern was downregulated in both cultivars, the global gene expression in the resistant cultivar was stronger than that in the susceptible cultivar. In addition, the expressed genes of two cultivars mostly differed in “cellular process,” “single-organism process,” “metabolic process,” and “response to stimulus” functional groups in the biological process Gene Ontology category: the upregulated differentially expressed genes (DEG) were largely enriched in the resistant cultivar, while the downregulated DEGs were largely enriched in the susceptible cultivar. Phenylpropanoid biosynthesis and phenylalanine metabolism are the key metabolic pathways in cotton in response to Fov. We found that lignin plays a potential role in cotton resistance to Fov. Two coding genes, caffeic acid 3-O-methyltransferase and peroxidase2 , as well as the two transcription factors MYB46 and MYB86 , are possibly involved in the accumulation and synthesis of lignin. Furthermore, the result showed that the quantification of lignin could be potentially used as a selection tool to identify Fusarium wilt resistant cotton.

Gut microbiome alterations and its link to corticosteroid resistance in immune thrombocytopenia - Yanan Wang; Fengqi Liu; Gaochao Zhang; Yan Su; Xueyan Sun; Qi Chen; Chencong Wang; Haixia Fu; Yun He; Xiaolu Zhu; Xiao Liu; Meng Lv; et al. (Science China Life Sciences, 2021)

Combining targeted sequencing and ultra-low-pass whole-genome sequencing for accurate somatic copy number alteration detection - Junfeng Fu; Weihua Guo; Cheng Yan; Zhenyang Lv; Yu Wang; Ze Wang; Zhe Fan; Ting Lei (Functional & Integrative Genomics, 2021)

Vertical bearing characteristics of rock-socketed pile in a synthetic soft rock - Bin Huang; Yuting Zhang; Bu Lv; Zhijun Yang; Xudong Fu; Benjiao Zhang (European Journal of Environmental and Civil Engineering, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Field tests of micro screw anchor piles under different loading conditions at three soil sites - Shi-Jin Feng; Wen-Ding Fu; Hong-Xin Chen; Hong-Xing Li; Yan-Li Xie; Shao-Feng Lv; Jin Li (Bulletin of Engineering Geology and the Environment, 2021)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

Arsenic trioxide alleviates acute graft-versus-host disease by modulating macrophage polarization - Xiao Liu; Yan Su; Xueyan Sun; Haixia Fu; Qiusha Huang; Qi Chen; Xiaodong Mo; Meng Lv; Yuan Kong; Lanping Xu; Xiaojun Huang; Xiaohui Zhang (Science China Life Sciences, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Contrasting effects of light, soil chemistry and phylogeny on leaf nutrient concentrations in cave-dwelling plants - Kundong Bai; Yigang Wei; Denan Zhang; Longfei Fu; Shihong Lv; Lili Deng (Plant and Soil, 2020)

Operation performance and microbial community of sulfur-based autotrophic denitrification sludge with different sulfur sources - Caixia Fu; Ji Li; Xiaomei Lv; Wei Song; Xiaolei Zhang (Environmental Geochemistry and Health, 2020)

Study on manufacturing process of ancient Chinese bi-metallic bronze Ge - Bingjie Li; Xudong Jiang; Yin Tu; Jianguo Lv; Qiang Fu; Bei Wei; Tao Hu; Chunxu Pan (Archaeological and Anthropological Sciences, 2020)

Physiological functions of urea transporter B - Lanying Yu; Tiantian Liu; Shuang Fu; Li Li; Xiaoping Meng; Xin Su; Zhanfeng Xie; Jiayan Ren; Yan Meng; Xuejiao Lv; Yanwei Du (Pflügers Archiv - European Journal of Physiology, 2019)
Urea transporters (UTs) are membrane proteins in the urea transporter protein A (UT-A) and urea transporter protein B (UT-B) families. UT-B is mainly expressed in endothelial cell membrane of the renal medulla and in other tissues, including the brain, heart, pancreas, colon, bladder, bone marrow, and cochlea. UT-B is responsible for the maintenance of urea concentration, male reproductive function, blood pressure, bone metabolism, and brain astrocyte and cardiac functions. Its deficiency and dysfunction contribute to the pathogenesis of many diseases. Actually, UT-B deficiency increases the sensitivity of bladder epithelial cells to apoptosis triggers in mice and UT-B-null mice develop II-III atrioventricular block and depression. The expression of UT-B in the rumen of cow and sheep may participate in digestive function. However, there is no systemic review to discuss the UT-B functions. Here, we update research approaches to understanding the functions of UT-B.

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Protective Effects of 1-Methylnicotinamide on Aβ1–42-Induced Cognitive Deficits, Neuroinflammation and Apoptosis in Mice - Lili Fu; Caihong Liu; Liang Chen; Yangge Lv; Guoliang Meng; Mei Hu; Yan Long; Hao Hong; Susu Tang (Journal of Neuroimmune Pharmacology, 2019)

Effects of Al Exposure on Mitochondrial Dynamics in Rat Hippocampus - Jisheng Nie; Shengjie Lv; Xueying Fu; Qiao Niu (Neurotoxicity Research, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Saikosaponin-d inhibits proliferation by up-regulating autophagy via the CaMKKβ–AMPK–mTOR pathway in ADPKD cells - Weiwei Shi; Dechao Xu; Junhui Gu; Cheng Xue; Bo Yang; Lili Fu; Shuwei Song; Dongmei Liu; Wei Zhou; Jiayi Lv; Ke Sun; Meihan Chen; et al. (Molecular and Cellular Biochemistry, 2018)

Pelagic larval dispersal habits influence the population genetic structure of clam Gomphina aequilatera in China - Yingying Ye; Zeqin Fu; Yunfang Tian; Jiji Li; Baoying Guo; Zhenming Lv; Changwen Wu (Genes & Genomics, 2018)

Phylogeographic analysis of porcine reproductive and respiratory syndrome virus 1 in Guangdong province, Southern China - Shao-Lun Zhai; Tao Lin; Xia Zhou; Zhang-Fu Pei; Zu-Zhang Wei; He Zhang; Xiao-Hui Wen; Qin-Ling Chen; Dian-Hong Lv; Wen-Kang Wei (Archives of Virology, 2018)

Effects of heat stress on piglet production/performance parameters - Zhenhua Guo; Lei Lv; Di Liu; Bo Fu (Tropical Animal Health and Production, 2018)

Impacts of Drought and Human Activity on Vegetation Growth in the Grain for Green Program Region, China - Hao Wang; Guohua Liu; Zongshan Li; Xin Ye; Bojie Fu; Yihe Lv (Chinese Geographical Science, 2018)

Novel method for iron recovery from hazardous iron ore tailing with induced carbothermic reduction-magnetic flocculation separation - Shao-Jun Bai; Chun-Long Li; Xiang-Yu Fu; Chao Lv; Shu-Ming Wen (Clean Technologies and Environmental Policy, 2018)

Imprinted gene expression in maize starchy endosperm and aleurone tissues of reciprocal F1 hybrids at a defined developmental stage - Meishan Zhang; Ruili Lv; Wei Yang; Tiansi Fu; Bao Liu (Genes & Genomics, 2018)

Morphological and molecular divergence of Rhipicephalus turanicus tick from Albania and China - Hong-Yu Li; Shan-Shan Zhao; Sándor Hornok; Róbert Farkas; Li-Ping Guo; Chuang-Fu Chen; Ren-Fu Shao; Ji-Zhou Lv; Yuan-Zhi Wang (Experimental and Applied Acarology, 2017)

Alpha-7 Nicotinic Receptor Signaling Pathway Participates in the Neurogenesis Induced by ChAT-Positive Neurons in the Subventricular Zone - Jianping Wang; Zhengfang Lu; Xiaojie Fu; Di Zhang; Lie Yu; Nan Li; Yufeng Gao; Xianliang Liu; Chunmao Yin; Junji Ke; Liyuan Li; Mengmeng Zhai; et al. (Translational Stroke Research, 2017)

Potential gray matter unpruned in adolescents and young adults dependent on dextromethorphan-containing cough syrups: evidence from cortical and subcortical study - Ying-wei Qiu; Xiao-fei Lv; Gui-hua Jiang; Huan-Huan Su; Xiao-fen Ma; Jun-zhang Tian; Fu-zhen Zhuo (Brain Imaging and Behavior, 2017)

Preferential flow characteristics of reclaimed mine soils in a surface coal mine dump - Lv Gang; Li Jun; Li Yexin; Wang Ting; Liu Yazhuo; Fu Xinyang (Environmental Monitoring and Assessment, 2017)

The Expression of Zinc Transporters Changed in the Intestine of Weaned Pigs Exposed to Zinc Chitosan Chelate - Mengyuan Lv; Xiongfeng Fu; Luansha Hu; Xiaojing Yue; Xinyan Han (Biological Trace Element Research, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Photodegradation of Mefenamic Acid in Aqueous Media: Kinetics, Toxicity and Photolysis Products - Ping Chen; Feng Liang Wang; Kun Yao; Jing Shuai Ma; Fu Hua Li; Wen Ying Lv; Guo Guang Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

NDH-1L interacts with ferredoxin via the subunit NdhS in Thermosynechococcus elongatus - Zhihui He; Fangfang Zheng; Yaozong Wu; Qinghua Li; Jing Lv; Pengcheng Fu; Hualing Mi (Photosynthesis Research, 2015)

Longitudinal changes of dopamine transporters in heroin users during abstinence - Shasha Xu; Ying Liu; Yu Li; Yangping Deng; Yiyun Huang; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Zhirui Guo; Mei Han; Xingdang Liu; et al. (Psychopharmacology, 2015)

Developmental expression and localization of MHC class I molecules in the human central nervous system - Aifeng Zhang; Hong Yu; Youji He; Yuqing Shen; Ying Zhang; Jiane Liu; Bo Fu; Dan Lv; Fengqin Miao; Jianqiong Zhang (Experimental Brain Research, 2015)

Dietary lipid concentrations influence growth and chemical and fatty acid compositions of juvenile redlip mullet, Liza haematocheila - Wenping Yang; Aimin Wang; Feng Gao; Yebing Yu; Linlan Lv; Fu Lv (Aquaculture International, 2015)

Capecitabine plus oxaliplatin (XELOX) compared with 5-fluorouracil/leucovorin plus oxaliplatin (FOLFOXs) in advanced gastric cancer: meta-analysis of randomized controlled trials - Hong-Bin Xu; Fang Huang; Rui Su; Fu-Ming Shen; Qian-Zhou Lv (European Journal of Clinical Pharmacology, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Photodegradation of Ibuprofen Under UV–Vis Irradiation: Mechanism and Toxicity of Photolysis Products - Fu Hua Li; Kun Yao; Wen Ying Lv; Guo Guang Liu; Ping Chen; Hao Ping Huang; Ya Pu Kang (Bulletin of Environmental Contamination and Toxicology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Phenotypic transition of corpus cavernosum smooth muscle cells subjected to hypoxia - Bodong Lv; Jianfeng Zhao; Fan Yang; Xiaojun Huang; Gang Chen; Kebing Yang; Shanshan Liu; Chunlei Fan; Huiying Fu; Zhaodian Chen (Cell and Tissue Research, 2014)

Multivariate control of root biomass in a semi-arid grassland on the Loess Plateau, China - Huoxing Zhu; Bojie Fu; Nan Lv; Shuai Wang; Jian Hou (Plant and Soil, 2014)

Characterization of the Promoter of Artemisia annua Amorpha-4,11-diene Synthase (ADS) Gene Using Homologous and Heterologous Expression as well as Deletion Analysis - Mengmeng Zhu; Fangyuan Zhang; Zongyou Lv; Qian Shen; Ling Zhang; Xu Lu; Weimin Jiang; Xueqing Fu; Tingxiang Yan; Lingxian Chen; Guofeng Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2014)

Molecular Cloning and Characterization of a Trichome-Specific Promoter of Artemisinic Aldehyde Δ11(13) Reductase (DBR2) in Artemisia annua - Weimin Jiang; Xu Lu; Bo Qiu; Fangyuan Zhang; Qian Shen; Zongyou Lv; Xueqing Fu; Tingxiang Yan; Erdi Gao; Mengmeng Zhu; Lingxian Chen; Ling Zhang; et al. (Plant Molecular Biology Reporter, 2014)

The maize d2003, a novel allele of VP8, is required for maize internode elongation - Hongkun Lv; Jun Zheng; Tianyu Wang; Junjie Fu; Junling Huai; Haowei Min; Xiang Zhang; Baohua Tian; Yunsu Shi; Guoying Wang (Plant Molecular Biology, 2014)

Polycyclic aromatic hydrocarbons and organochlorine pesticides in rice hull from a typical e-waste recycling area in southeast China: temporal trend, source, and exposure assessment - Fang Liu; Chunyang Liao; Jianjie Fu; Jungang Lv; Qinzhao Xue; Guibin Jiang (Environmental Geochemistry and Health, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

Cloning of lipoprotein lipase (LPL) and the effects of dietary lipid levels on LPL expression in GIFT tilapia (Oreochromis niloticus) - Aimin Wang; Guangming Han; Zhitao Qi; Fu Lv; Yebing Yu; Jintian Huang; Tian Wang; Pao Xu (Aquaculture International, 2013)

Promoting role of an endophyte on the growth and contents of kinsenosides and flavonoids of Anoectochilus formosanus Hayata, a rare and threatened medicinal Orchidaceae plant - Fu-sheng Zhang; Ya-li Lv; Yue Zhao; Shun-xing Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine - Ya-fei Shi; Ju-fang Chi; Wei-liang Tang; Fu-kang Xu; Long-bin Liu; Zheng Ji; Hai-tao Lv; Hang-yuan Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Expression of R132H Mutational IDH1 in Human U87 Glioblastoma Cells Affects the SREBP1a Pathway and Induces Cellular Proliferation - Jian Zhu; Gang Cui; Ming Chen; Qinian Xu; Xiuyun Wang; Dai Zhou; Shengxiang Lv; Linshan Fu; Zhong Wang; Jianling Zuo (Journal of Molecular Neuroscience, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Evaluation of urban sprawl and urban landscape pattern in a rapidly developing region - Zhi-qiang Lv; Fu-qiang Dai; Cheng Sun (Environmental Monitoring and Assessment, 2012)

Molecular characterization and expression analysis of dihydroflavonol 4-reductase (DFR) gene in Saussurea medusa - Houhua Li; Jian Qiu; Fudong Chen; Xiaofen Lv; Chunxiang Fu; Dexiu Zhao; Xuejun Hua; Qiao Zhao (Molecular Biology Reports, 2012)

Three-dimensional evaluation of upper anterior alveolar bone dehiscence after incisor retraction and intrusion in adult patients with bimaxillary protrusion malocclusion - Qing-yuan Guo; Shi-jie Zhang; Hong Liu; Chun-ling Wang; Fu-lan Wei; Tao Lv; Na-na Wang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2011)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Frequency of double minute chromosomes and combined cytogenetic abnormalities and their characteristics - Yihui Fan; Renfang Mao; Hongpei Lv; Jie Xu; Lei Yan; Yanhong Liu; Meng Shi; Guohua Ji; Yang Yu; Jing Bai; Yan Jin; Songbin Fu (Journal of Applied Genetics, 2011)

Silencing USP22 by asymmetric structure of interfering RNA inhibits proliferation and induces cell cycle arrest in bladder cancer cells - Lei Lv; Xing-yuan Xiao; Zhao-hui Gu; Fu-qing Zeng; Lu-qi Huang; Guo-song Jiang (Molecular and Cellular Biochemistry, 2011)

Selection and characterization of a high-temperature tolerant strain of Porphyra haitanensis Chang et Zheng (Bangiales, Rhodophyta) - Xing-Hong Yan; Feng Lv; Chang-Jun Liu; Yue-Fu Zheng (Journal of Applied Phycology, 2010)

Insulin inhibits myocardial ischemia-induced apoptosis and alleviates chronic adverse changes in post-ischemic cardiac structure and function - Wenjuan Xing; Wenjun Yan; Feng Fu; Yulan Jin; Lele Ji; Wenchong Liu; Li Wang; Anlin Lv; Yunyan Duan; Jun Zhang; Haifeng Zhang; Feng Gao (Apoptosis, 2009)

Protein phosphatase 1A (PPM1A) is involved in human cytotrophoblast cell invasion and migration - Baohua Zhang; Zhi Zhou; Haiyan Lin; Xiaoyin Lv; Jiejun Fu; Ping Lin; Cheng Zhu; Hongmei Wang (Histochemistry and Cell Biology, 2009)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Polymorphisms in genes involved in folate metabolism as maternal risk factors for Down syndrome in China - Shao-shuai Wang; Fu-yuan Qiao; Ling Feng; Juan-juan Lv (Journal of Zhejiang University-SCIENCE B, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)